The hippocampus under influence: structural effects of synthetic and natural psychotropic medications - Melissa Santaya; Halford Warlick; Causicaa Chandramohan; Prathmica Chandramohan; Armena Jafarmadar; Ernesto Joubran; Marianne Koleng; Christina Regine Owens-Charles; Jorge Rubinos Rodriguez; Madeline Sardinas; Leah Simon; Stephanie Singer; et al. (Molecular Biology Reports, 2026)

Forest conversion is more strongly associated with soil microbial functioning than chronic trace element exposure in an industrialized coastal mediterranean ecosystem - S. Fabian Plaza; F. Gonzalo Tortella; Giovanni Larama; Rodrigo Rodriguez; Thierry Lebeau; Clémentine Lapie; Walter Valdivia; Eros Fajardo; M. Fernández-Baldo; Juan Hirzel; Gustavo Santoyo; Mauricio Schoebitz (Environmental Pollution, 2026)

Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

A scoring system for validity assessment of biomarkers of food intake - Christoph Hassenberg; Carina I. Mack; Claudia Favari; Sylvie Baier; Ramon Estruch; Gabi Kastenmüller; Rosa Lamuela-Raventós; Rikard Landberg; Pedro Mena; Costanza Michelini; Stefania Noerman; Ana Rodriguez-Mateos; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Spatially resolved groundwater and river nutrient inputs to Baltic Sea coastal waters via radium isotopes - Aprajita S. Tomer; Tristan McKenzie; Claudia Majtényi-Hill; Ceylena Holloway; Júlia Rodriguez-Puig; Gloria Reithmaier; Linnea Henriksson; Beata Szymczycha; Isaac R. Santos (Marine Chemistry, 2026)

Shrimp (sub-)national traceability and retail fraud detection using stable isotopes and multi-element profiling - V. Deklerck; R.P. Davis; A. Rodriguez-Zunino; S. Khongtanakrittakorn; S. Hofem; J. Jungkeit; A. Leyton; M. Osorto-Nuñez; C. Podmore; L. Prior; C.C. Smith; B. Soule; et al. (Food Control, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Hypertrophic cardiomyopathy-linked Tnnc1 variants are associated with distinct myopathic changes in slow skeletal muscle of mice - Sonu Patel; Gabriel Leite da Silva Santos; Jaelynn Florence; Aida Rahimi Kahmini; Yun Shi; Michelle Rodriguez Garcia; Bradley S. Gordon; P. Bryant Chase; Christopher Solís; Orlando Laitano; J. Renato Pinto; Michelle S. Parvatiyar (Journal of Muscle Research and Cell Motility, 2026)

Low-dose inorganic arsenic exposure reprograms macrophages differentiation and function toward tumor-promoting phenotypes - Emily J. Illingworth; Sylvia S. Sanchez; Kristal A. Rychlik; Andre Kleensang; Jason Laird; Gabriel A. Lopez-Cecetaite; M. Carolina Rodriguez Steube; Aakriti Mathur; Pritam Sadhukhan; Daniel A. Medina-Cleghorn; Daniel Nomura; Martyn T. Smith; et al. (Environmental Research, 2026)

Prevalent detection of multiclass environmental chemicals in paired CSF and plasma samples and their potential associations with postpartum depressive symptoms in pregnant women - Bushra Amreen; Corina Lesseur; Ravikumar Jagani; Hiraj Patel; Daniel Katz; Joshua Hamburger; Noel Strong; Leah Habersham; Anna-Sophie Rommel; Lotje D. de Witte; Chris Gennings; M Mercedes Perez-Rodriguez; et al. (Environmental Research, 2026)

First Report of Gynandromorphism in Rhipicephalus microplus (Acari: Ixodidae) in El Salvador - Marvin Stanley Rodriguez Aquino; Esther Noemí Juárez Alvarado; Francisco Javier Castaneda Lúe; Pamela Michelle Cornejo Rivas; Melissa S. Nolan; Lídia Gual-Gonzalez (Acta Parasitologica, 2026)
Purpose Gynandromorphism is a developmental anomaly characterized by the simultaneous presence of male and female sexual morphological traits within the same individual. This study documents a case of gynandromorphism in the cattle tick Rhipicephalus microplus (Canestrini 1888) in El Salvador. Methods The specimen was collected from a bovine belonging to the Experimental and Practical Station of the Faculty of Agronomic Sciences of the University of El Salvador, located in the municipality of San Luis Talpa, Department of La Paz. Results The reported gynandromorph of R. microplus exhibits bilateral gynandromorphism, displaying primarily female characteristics on the left side and male characteristics on the right. Conclusion This is the first report of a tick with gynandromorphism in El Salvador. Further studies are warranted to understand the implications of such anomalies and their veterinary and public health relevance.

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

A GIS–AHP Framework for Sustainable Well Placement: Application for Natural Gas and Hydrogen Exploration in the Eastern Cordillera Basin, Colombia - Salim A. Salon; Sebastian S. Rodriguez; Jhon M. Muñoz-Barrera; Fabián Gallego; Cesar Mora; Deysi P. Forero; Jose F. Osorno; Cristian Peñafort (Natural Resources Research, 2026)

SnRK1 subcellular localization is linked to TOR signaling, chloroplast function, and salt stress tolerance in mature Arabidopsis leaves - Ana Paula Lando; Paula C. Maritano; Giuliano Barbieri; Danilo Daloso; Giselle M.A. Martínez-Noël; Marianela S. Rodriguez (Plant Science, 2026)

Biocrust belt below the edge of a dying glacier in the Tropical Andes - Alejandro Salazar; Maria E. Gutiérrez-Lagoueyte; Ingibjörg S. Jónsdóttir; Isabel C. Barrio; Heiðrún I. Guðmundsdóttir; Emilio Rodriguez-Caballero; Adriana Sanchez (Alpine Botany, 2026)
On recently deglaciated terrain, soil instability can be a physical barrier limiting seedling establishment. Here we used a space-for-time approach to study the role of biological soil crust (biocrust) as soil surface stabilizer and facilitator of ecological succession along a glacier forefield chronosequence at the retreating Conejeras glacier in the Tropical Andes. We used the point-intercept method to estimate surface cover of plants, biocrust, bare ground and rocks, as well as soil surface roughness; and a field soil aggregate kit to estimate soil stability. As hypothesized, following a bare-ground stage near the edge of the glacier, the successional trajectory involved the development of a biocrust belt, including bryophytes and lichens, followed by an increasing vascular plant cover. The development of biocrust was accompanied by higher soil surface roughness and soil stability, which likely increased seed entrapment and seedling establishment. Our results suggest that the development of cyanobacterial-dominated biocrust at the forefield of the Conejeras glacier may favor the establishment of plants with large seeds, such as graminoids from the Festuca genus. Overall, our findings highlight the key role of biocrusts in the ecological dynamics that follow glacier melt in the Tropical Andes.

Community structure and residence time of fishes associated with select soft coral taxa in Anda, Pangasinan, northwestern Philippines - Romina Therese S. Lim; Cleto L. Nañola; Maria Vanessa Baria-Rodriguez (Aquatic Ecology, 2026)

Transcriptomic response of Acropora cervicornis following transplantation to a marginal, nearshore environment - Allyson DeMerlis; Colin Foord; Dalton J. Hesley; Richard F. Karp; Lys M. Isma; Natalia Andrade-Rodriguez; Kevin H. Wong; Michael S. Studivan; Mike Jankulak; Andrew C. Baker; Diego Lirman; Nikki Traylor-Knowles; et al. (Frontiers in Marine Science, 2026)
As reef-building coral cover has declined worldwide, coral restoration has become a widespread response towards repopulating degraded reefs. In-situ nurseries have provided refugia for the regrowth of several coral species, yet long-term success following outplanting remains highly variable, particularly when corals are introduced into novel or marginal environments. Additionally, while growth and survivorship are commonly used to evaluate restoration success, molecular responses may also provide critical insights into the capacity of corals to acclimatize following transplantation. Here, we examined host and algal symbiont gene expression in the critically endangered reef-building coral Acropora cervicornis following transplantation from an offshore nursery in Key Biscayne, Florida to a nearshore, urbanized habitat in the Port of Miami, Florida. Three nursery-propagated genotypes were outplanted in June 2021 and sampled after four months at both sites for transcriptomic analysis ( n =12 after quality filtering). Transplanted corals exhibited significant shifts in host gene expression relative to nursery controls, with 961 host and symbiont genes significantly upregulated and 165 significantly downregulated. Upregulated host genes were predominantly associated with the environmental stress response, including heat shock proteins, unfolded protein binding, apoptotic processes, detoxification pathways, and innate immune signaling. Weighted gene co-expression network analysis identified two host modules positively associated with the nearshore outplant site and were enriched for pathways related to protein folding, immune activity, and cellular reorganization. These results demonstrate that A. cervicornis outplanted to a nearshore, urbanized environment exhibits sustained activation of stress- and immune-related molecular pathways months after transplantation, which is consistent with a stress-response profile that may reflect ongoing acclimatization. Integrating molecular diagnostics with environmental monitoring may refine genotype and site selection to enhance restoration outcomes.

Modelling primary production: multitude of theories, or multitude of languages? - Jozef Skákala; Shubha Sathyendranath; Yuri Artioli; Deep S. Banerjee; Heather Bouman; Robert J. W. Brewin; Momme Butenschön; Stefano Ciavatta; Stephanie Dutkiewicz; Yanna Fidai; David Ford; Grinson George; et al. (Ocean Science, 2026)
Marine primary production, converting approximately 50 Gt of inorganic carbon into organic carbon per year, is an important component of the global carbon cycle, and a major determinant of past, present and future climate. Large-scale, long-term estimates of marine primary production rely primarily on two types of models: satellite-based models that make extensive use of remote-sensing data, and ecosystem models providing numerical simulation of ecological processes embedded in general ocean circulation models. Intercomparison exercises of model outputs (both within and across the two model types) have consistently revealed high discrepancies between estimated global ocean primary production, including divergent magnitudes and even opposite trends. Model-observation comparisons are also complex, because paucity of data, differences in measurement techniques, and evolving methodologies could all lead to difficulties with the interpretation of results. These uncertainties limit the applications of primary production models (both satellite-based and ecosystem), especially in the climate context, where an important question is whether climate change will drive significant future changes in regional or global primary production. Both satellite-based and ecosystem models rely on a range of fixed model parameters, whose values need to be carefully estimated and tested. In this paper, we suggest that such model parameters represent an underappreciated but important source of inter-model differences. With the proliferation of both satellite and in situ observations of relevant variables at global scales, and the availability of powerful statistical tools such as data assimilation and machine learning, we argue that time is right to systematically examine model parameters, gaining both better insights into parameter values and how those values might vary in space and time. We argue that such spatio-temporal parameter variability can be theoretically justified for ecosystem models with complexity similar to those commonly used within Earth System Models (ESMs) in climate studies. The spatially and temporally varying parameter values could serve to unify models that are structurally different. An important aspect of this unification could be the ability to infer the spatio-temporal variability of parameters in the less complex models from the emergent behaviour of the more complex ones. This could include ecosystem model simulations of nutrients, temperature, phytoplankton classes, or vertical distributions informing satellite-based models. We conclude that better understanding of model parameter roles and integration (or inter-calibration) of different types of models could reduce discrepancies among the primary production models and improve the reliability of marine primary production projections.

Encapsulation of tyrosinase in liposomes: A biomimetic approach to efficient biodetection of polyphenols in grape juice - Priscila Alessio; Cibely S. Martin; Mateus D. Maximino; Matheus S. Pereira; Constantin Apetrei; Maria L. Rodriguez-Mendez (Journal of Food Engineering, 2026)

Ground level enhancement GLE #77 on 11 November 2025: a data summary - A.L. Mishev; B. Heber; K.-L. Klein; R. Vainio; H. Mavromichalaki; O. Raukunen; N. Larsen; N. Petrov; N. Nikonov; S. Masson; M. Pesce-Rollins; B.T. Kress; et al. (Advances in Space Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Enzymatic degradation of proteinaceous Pickering particles – A strategy to induce demulsification - Gloria Hernandez-Rodriguez; Zijing Wu; David Harbottle; Brent S. Murray; Anwesha Sarkar (Food Chemistry, 2026)

Petiole Nitrate Analysis: A Diagnostic Method for Optimizing Nitrogen Management in Potato - C. M. Giletto; W. Carciochi; S. E. Silva; M. N. Cassino; S. Rodriguez; J. C. Laborde Amador; E. C. Zamuner; N. I. Reussi Calvo (Potato Research, 2026)

Contributions to the knowledge of DNA barcodes and diversity of intertidal and shallow-water mollusks in the Beagle Channel - L. D. Chiberry; J. Sánchez; V. M. Núñez; S. Rodriguez; M. Pellegrino; S. Poljak (Polar Biology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Impacts of Diverse Stakeholder Participation on Fisheries Management - Sangeeta Mangubhai; S. L. Smith; Z. Davis; N. Koedyker; J. Augustyn; D. Durholtz; S. Fulton; Harlisa; M. T. Hidayat; L. Hiriart-Bertrand; M. Khazali; E. Litsinger; et al. (Coastal Management, 2026)

Use of shotgun immunoproteomics for the development of protein vaccines against Edwardsiella piscicida - Kim L. Jacobsen; Matt J. Griffin; Brett S. Phinney; Michelle Salemi; Zeinab Yazdi; Sujita Balami; Caitlin E. Older; Cynthia C. Ware; Fernando Y. Yamamoto; Noor-ul Huda; Tania Rodriguez-Ramos; Brian Dixon; et al. (Fish & Shellfish Immunology, 2026)

Associations between exposure to metals, chlorinated pesticides, and PCBs and differential leukocyte profiles in Flemish adolescents - Fen Zhang; Lützen Portengen; Hamid Y. Hassen; Laura Rodriguez Martin; Madeline Carsique; Amélie Crépet; Jasper Engel; Jacob Van Klaveren; Nicolas Van Larebeke; Willy Baeyens; Stefaan De Henauw; Tim S. Nawrot; et al. (Environmental Research, 2026)

Effect of Probiotics on Sperm Quality in the Adult Mouse - Ana Sanchez-Rodriguez; Ingrid I. D. Idrovo; Rocío Villafranca; Nerea Latorre; Juan Antonio Rielo; Ane Laburu; Sandra Nieto-Román; Daniel Heredia; Rubén González; Virginia García-Cañas; Diego Laxalde; Carolina Simó; et al. (Probiotics and Antimicrobial Proteins, 2025)
The administration of probiotics for the treatment of different diseases has gained interest in recent years. However, few studies have evaluated their effects on reproductive traits. The objective of this study was to examine the effect of two mixtures of probiotics, a commercial probiotic (Vivomixx®) and a mix of Lacticaseibacillus rhamnosus GG and Faecalibacterium duncaniae A2-165, on sperm quality in a mouse model. Adult male mice (8 months old) were used for two experimental and one control groups ( n = 5 each). The probiotics or physiological serum (control) was administered orally, twice a week, during 5 weeks. Sperm were collected from the cauda epididymis, and their total number, motility, kinematics, morphology, and acrosome integrity were assessed in recently collected samples and after a 60-min in vitro incubation. Results showed a higher percentage of normal sperm in both experimental groups, with fewer head abnormalities than in the control. Differences were found among groups in the morphometry of sperm heads, being more elongated in mice treated with probiotics. Sperm from probiotic-treated mice showed similar total motility when compared to the controls, although the proportion of progressively moving sperm and their vigor of motility were lower. Sperm swimming descriptors were measured with a CASA system. Velocity parameters were similar among groups whereas linearity was higher in mice treated with the commercial probiotic. These results suggest that the administration of probiotics may increase the proportion of sperm with normal morphology and lead to modifications in sperm head shape that may enhance sperm swimming. Studies using a longer administration period would be useful in further characterizing the effect of these probiotic mixtures on sperm quality and fertilization capacity.

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

The role of emersion time in modulating biomarker responses to pollution in intertidal mollusks - María V. Laitano; Clara Liebana; Ivana S. Friedman; Yamila E. Rodriguez (Marine Environmental Research, 2025)

Discovery of Latissimia ningalooensis: a new invasive soft coral species in Puerto Rico - Daniel A. Toledo-Rodriguez; Catherine S. McFadden; Nilda M. Jimenez Marrero; J. David Muñoz-Maravilla; Alex J. Veglia; Ernesto Weil; Nikolaos V. Schizas (Biological Invasions, 2025)

The key mechanisms associated with the survival of Gulf toadfish, Opsanus beta , when in severe hypoxia - Anastasiya Plotnikova; Isabelle R. Nelson; Shara Y. Sookhoo; Jacob M. Belkin; Vanessa P. Lima; Ross D. Bronfman Bunch; Athena M. Santomero; Sophia A. Santomero; Emily C. Rodriguez; Jayda K. Rodriguez; Kathleen M. Davis; Amanda J. Kaplan; et al. (Journal of Fish Biology, 2025)
Florida's shallow seagrass beds experience daily diurnal fluctuations in environmental oxygen, leading to hypoxic episodes (PO 2 −1 , ~6 kPa) that have increased in frequency and intensity in recent decades. The native Gulf toadfish ( Opsanus beta ) have been shown to employ a suite of adaptive cardiovascular, ventilatory and metabolic adjustments to survive moderate hypoxia, but little is known of the mechanisms used to survive severe hypoxia. The objective of this study was to characterize the acute response of Gulf toadfish to severe hypoxia ( 2 ~0.4 kPa for 3 h followed by 1 h recovery). Heart rate, pulse pressure, caudal arterial blood pressure, ventilation frequency and ventilation amplitude were monitored and blood samples were taken from both groups and analysed for pH, glucose, lactate and other endpoints. Hypoxia‐exposed fish experienced a statistically significant 70% decrease in heart rate and a 32% decrease in ventilation frequency during hypoxia exposure. Moreover, plasma glucose concentrations increased 5‐fold and plasma lactate concentrations increased 6‐fold, with a minimal reduction in pH. Our findings support our hypothesis that Gulf toadfish are highly hypoxia tolerant and survive severe hypoxia by reducing energy expenditure and switching to anaerobic metabolism. It is important to understand how the Gulf toadfish deal with severe hypoxia due to the increasing prevalence of severe hypoxia in its natural environment.

Human Footprint Halves Tail Loss Rates in Geckos Worldwide - Lucas Rodriguez Forti; Ana Marta Pereira R. da S. Passetti; Gabriela Fonseca; Maria Eduarda Lima‐Alves; Jandson Lucas Camelo da Silva; Marcus Dantas; Marcelo Henrique Torres de Medeiros; Luís Gustavo de Oliveira Santos; Marcos S. L. Figueiredo; Judit K. Szabo (Global Ecology and Biogeography, 2025)
Aim Anthropogenic changes alter predator–prey systems worldwide. Defensive behaviour is shaped by the costs and benefits for individuals, and we hypothesise that tail shedding, as an escape strategy, has a higher cost for animals in human‐modified environments compared to natural landscapes. Therefore, our central objective was to evaluate the effects of human footprint on the observed frequency of caudal autotomy in geckos. Location Global. Time Period 1964–2023. Major Taxa Studied Lizards. Methods We classified caudal condition as intact, amputated and regenerated in over 140,000 images of 1264 gecko species in the citizen science platform iNaturalist. We included a quantification of tail abnormalities and tested the effects of the Human Footprint Index, body size, habitat preference, and climate variables on autotomy and regeneration rate using two beta‐binomial models. We also reviewed records of caudal autotomy in the literature, searching for relevant articles published in the Web of Science, Scopus and Scientific Electronic Online databases. Results We identified 14,382 cases of shed or regenerated tail in 748 species among iNaturalist observations. For 631 of these species, autotomy has not yet been described in the scientific literature. We observed caudal abnormalities in 36 species. Tail loss rates dropped from approximately 25% to less than 12% in areas with the highest Human Footprint Index, indicating a strong spatial association between anthropogenic pressure and reduced autotomy. Saxicolous and smaller geckos, independently of phylogeny, had a higher rate of tail loss. Main Conclusions We found that gecko tail loss dropped > 50% in areas with high human impact. Despite the increasing number of observations, rates of caudal autotomy decreased from 13.3% in 2000–2011 to 9.7% in 2012–2023, suggesting a trend that could be related to changes in predation pressure or the potential loss of autotomy among geckos under increased anthropogenic landscape transformation.

Evaluating Ecological Restoration Through Natural Regeneration Requires Replicated Landscape‐Scale Monitoring Studies - Michiel van Breugel; Maria Elizabeth Rodriguez‐Ronderos; Jefferson S. Hall; Daisy Dent; Dylan Craven (Global Change Biology, 2025)

Integrated Population Pharmacokinetic-pharmacodynamic Modeling of HIV Virus-host Infection Dynamics in Patients Undergoing Antiretroviral Monotherapy - Alberto Vegas Rodriguez; Nieves Velez de Mendizábal; Yanan Zheng; Jason T. Hindman; Ramesh Palaparthy; John Ling; Iñaki F. Trocóniz; Ana Ruíz-Garcia; Justin S. Feigelman (The AAPS Journal, 2025)
Chronic human immunodeficiency virus (HIV) infection continues to pose a major global health challenge, with an estimated 39.9 M cases and 1.3 M new infections per year. Up to 75%, of people with HIV (PWH) are currently being treated with antiretroviral therapy. The development of effective treatments for HIV requires a detailed understanding of the virus-host interaction. Often, mathematical models are used to inform this understanding as well as to characterize therapeutic response. This work aims to develop a single and fully identifiable population semi-mechanistic pharmacokinetic/pharmacodynamic (popPKPD) model integrating data (drug levels, CD4 + T cells and viral RNA) of five different antiretroviral (ARV) drugs administered in monotherapy: lenacapavir, bictegravir, tenofovir alafenamide, emtricitabine and elvitegravir. Data were obtained from six phase 1 clinical studies and model development was performed using NONMEM 7.5.1. The viral dynamics were best described by expanding the “basic” viral dynamics model with two more populations of infected cells: chronically and latently infected. Obtained death rates values of infected cells & virus were consistent with literature values. Population baseline HIV-RNA was estimated to be 43,460 copies/mL, with an IIV of 141%, the estimated baseline concentrations of CD4 + cells varied largely across the different cell types in the model: 410, 20, 7 and 7 cells/mL for uninfected, infected, chronic and latently infected cells, respectively. The popPKPD model was able to capture key aspects of viral dynamics, drug behaviour, and treatment response. The models developed will serve as a useful tool for further development and optimization of these HIV therapies, especially when evaluating multiple ARVs to be administered in a novel combination setting. Graphical Abstract

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Biogenic nanoparticles: Synthesis, characterization, applications and scaling up limitations in water treatment - Alejandra Ortiz-Tirado; Luisa F. Medina-Ganem; Erick R. Bandala; Alain S. Conejo-Davila; Alejandro Vega-Rios; Ashantha Goonetilleke; Oscar M. Rodriguez-Narvaez (Journal of Environmental Chemical Engineering, 2025)

Development of a biotechnological process for the production of recombinant canine interferon-alpha using the baculovirus-insect cell and larvae system - Maria S. Rodriguez; Ignacio Smith; Marcela S. Villaverde; Joaquin M. Birenbaum; Joaquin Poodts; Federico J. Wolman; Alexandra M. Targovnik; Maria V. Miranda (Biotechnology Letters, 2025)

Multi-wavelength internal standardization using inductively coupled plasma optical emission spectrometry - Reagan Elia; Thomas J. Johnston; Alberto D. Figueroa; Emily M. Curbow; Mayra S. Gonzalez Guzman; Leah C. Rodriguez Cabrera; Marisa M. Morcom; Willis B. Jones (Analytica Chimica Acta, 2025)

P20-17 Polyethylene terephthalate (PET) nanoplastics induce acute pulmonary inflammation in mice - Ø.P. Haugen; L.M.A. Camassa; H.F. Berntsen; F.-C. Lin; V. Alcolea-Rodriguez; R. Portela; F. Barbero; O.A.H. Foss; H. Sadeghiankaffash; Ø. Skare; S. Alsaedi; A.L. Moen; et al. (Toxicology Letters, 2025)

Understanding urban tree heat and drought stress by tracking growth and recovery following an extreme year - Renée M. Marchin; Manuel Esperon-Rodriguez; Mark G. Tjoelker; David S. Ellsworth (Landscape and Urban Planning, 2025)

Characterization of agr-like Loci in Lactiplantibacillus plantarum and L. paraplantarum and Their Role in Quorum Sensing and Virulence Inhibition of Staphylococcus aureus - Weizhe Wang; Ifigeneia Kyrkou; Martin S. Bojer; Dina Kalloubi; Abdul Jabbar Kali; Miguel Alena-Rodriguez; Jørgen J. Leisner; Stephanie Fulaz; Hanne Ingmer (Probiotics and Antimicrobial Proteins, 2025)
The pathogenicity of Staphylococcus aureus is largely regulated by the agr quorum sensing (QS) system encoded by agrBDCA , which coordinates virulence factor production through secretion and sensing of auto-inducing peptides (AIPs). agr -like systems are also present in coagulase-negative staphylococci, and several of these encode AIPs that inhibit S. aureus QS. In lactic acid bacteria, a similar locus was previously identified in Lactiplantibacillus plantarum WCSF1 termed lamBDCA . Here, we characterized the lamBDCA locus in L. plantarum LMG 13556 and L. paraplantarum CIRM-BIA 1870, and explored the effects on S. aureus QS. Notably, we found that co-cultivation with L. paraplantarum significantly inhibits S. aureus QS and hemolysin production, while less so for L. plantarum . The inhibition by L. paraplantarum was lost upon disruption of its lamBDCA locus, suggesting that the L. paraplantarum AIP mediates cross-species interference with S. aureus agr activation. Transcriptomic analysis revealed that lamBDCA in L. paraplantarum controls the expression of genes belonging to various functional categories, including stress response and metabolism. The latter includes genes encoding riboflavin (B2 vitamin) biosynthesis, which enabled the growth of the L. paraplantarum lamB mutant in the presence of roseoflavin, a toxic riboflavin analogue. Collectively, our results show that L. paraplantarum CIRM-BIA 1870 interferes with S. aureus virulence gene expression through QS suppression, and they implicate QS in the probiotic properties of L. paraplantarum .

Shadows over Caribbean reefs: occurrence of a new invasive soft coral species, Xenia umbellata, in southwest Puerto Rico - Daniel A. Toledo-Rodriguez; Alex J. Veglia; Nilda M. Jimenez Marrero; Joyce M. Gomez-Samot; Catherine S. McFadden; Ernesto Weil; Nikolaos V. Schizas (Coral Reefs, 2025)

Evaluating 3D-Printed Pre-separator Inserts in a Fast Screening Impactor for Physicochemical Characterization of Fine Particle Dose Release from Dry Powder Inhalers - Nathan A. Reed; Roee Dar; Nicholas Holtgrewe; Leo N. Y. Cao; Xiaofei Liu; Denise S. Conti; Bryan Newman; Elizabeth Bielski; Jason D. Rodriguez; Changning Guo (AAPS PharmSciTech, 2025)

Correction: Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Subclinical infection and localization of foot-and-mouth disease viral RNA/antigens in apparently healthy Asiatic buffalo under natural condition - Rajeev Ranjan; Jitendra K. Biswal; Nandakumar S. Nair; Karam Pal Singh; Biswajit Das; Jajati Keshari Mohapatra; Saravanan Subramaniam; Manoranjan Rout; Jonathan Arzt; Luis L. Rodriguez; Bramhadev Pattnaik (Veterinary Microbiology, 2025)

Lignin hydrotreatment to aromatics products on metallic phosphides carbon-based catalysts produced from lignin - M. García-Rollán; S. Bertran-Llorens; M.A. Palazzolo; P.J. Deuss; H.J. Heeres; R. Ruiz-Rosas; J.M. Rosas; J. Rodriguez-Mirasol; T. Cordero (Fuel, 2025)

Understanding osmoregulation, cryoprotectant toxicity, and cold tolerance in sea urchin eggs: Implications for cryopreservation - S. Campos; Uxía Rodriguez; J. Troncoso; E. Paredes (Cryobiology, 2025)

Biomechanical and Compositional Changes in the Murine Uterus with Age - Mari J. E. Domingo; Triniti N. Vanoven; Raffaella De Vita; Maria E. Florian Rodriguez; Kristin S. Miller; Isaac J. Pence (Annals of Biomedical Engineering, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

Temporal invasion regime attributes influence community synchrony and stability in an arid land system - Clarissa S. Rodriguez; Lynn Sweet; Melanie Davis; Scott Heacox; Cameron Barrows; Loralee Larios (Ecology, 2025)
Invasive species have become a major threat to ecosystems across the globe, causing significant ecological and economic damage. To anticipate how communities may respond to future invasions, it is crucial to refine how invader impacts are evaluated, especially in historically uninvaded and highly variable systems such as arid lands. While invader abundance is typically used to predict invader impacts, it may not effectively capture the dynamics that occur over time for established invaders that experience cyclical dynamics (i.e., boom‐bust patterns), making it more challenging to track invader impacts. To address this issue, we leveraged a long‐term vegetation dataset to develop a novel invasion regime framework for a dominant annual invader in North American deserts, Brassica tournefortii . Using abundance data over time, we evaluated how attributes of this invader's boom‐bust dynamics (i.e., invasion level, boom frequency and magnitude) influence the long‐term synchrony and stability of invaded Eolian sand dunes communities. We found that attributes that captured the temporal effects of the invader were strong indicators of the impacts of an invader on long‐term attributes of communities. Specifically, the mean magnitude of invader booms led to a decrease in species asynchrony and community stability. Increasing boom frequency also decreased community stability, but this was more muted. Mean magnitude of invader booms also mediated shifts in the relationship between synchrony and stability, with this relationship becoming more shallow with increasing boom magnitudes. Our research emphasizes the significance of using community metrics that capture temporal dynamics to document invasion impacts within dynamic arid land systems. The invasion regime framework can additionally offer insights into the mechanisms that may enable the persistence of the invader over time. Together, this knowledge can be helpful in guiding decision‐making and land management strategies aimed at effectively controlling and mitigating the impact of invasive species.

Perceptions and Attitudes of Drinking Water Supply Systems Staff Towards Climate Change Adaptation for Drinking Water Quality Management - S. M. Cynthia Compaoré; Ianis Delpla; Sonja Behmel; Manuel J. Rodriguez (Environmental Processes, 2025)

Unveiling the biogas potential of raw Agave leaf juice: Exploring a novel biomass source - Maiki S. de Paula; Oscar F. Herrera Adarme; Maria Paula C. Volpi; Carla I. Flores-Rodriguez; Marcelo F. Carazzolle; Gustavo Mockaitis; Gonçalo A.G. Pereira (Biomass and Bioenergy, 2025)

The use of lichens and mosses as sentinel organisms for the determination of the airborne organic pollution in Western Pyrenees: The case of the Irati forest - J. Bustamante; A. Gredilla; O. Liñero; D. Amouroux; D. Elustondo; J.M. Santamaría; A. Rodriguez-Iruretagoiena; S. Fdez-Ortiz de Vallejuelo; G. Arana; A. de Diego (Atmospheric Pollution Research, 2025)

Phytoremediation potential of Tripogandra diuretica for chromium and lead contaminated soils - S. Carusso; N. Rodriguez; Á. B. Juárez; Y. El Kassisse; V. Rodriguez Salemi; L. I. de Cabo (International Journal of Environmental Science and Technology, 2025)

Microplastics in the digestive tract of an endangered cetacean of the Southwest Atlantic Ocean: The franciscana dolphin - Antonella D. Padula; Ana C. Ronda; Lucas S. Rodríguez Pirani; A. Lorena Picone; Rosana M. Romano; Gisela V. Giardino; Juan Pablo Seco Pon; Rodrigo Machado; Marcela Gerpe; Diego Rodriguez; Pablo Denuncio (Marine Pollution Bulletin, 2025)

Assessment of watershed health, integrating environmental, social, and climate change criteria into a fuzzy logic framework - S. Rodriguez-Flores; C. Muñoz-Robles; J.A. Quevedo Tiznado; P. Julio-Miranda (Science of The Total Environment, 2025)

Characterization of coral communities in the shallow hydrothermal vents of Mabini, Batangas, Philippines - Joana Andrea C. Maningas; Victor S. Ticzon; Maria Vanessa B. Rodriguez (Regional Studies in Marine Science, 2025)

Bacterial dynamics and volatile metabolome changes of vacuum-packaged beef with different pH during chilled storage - Magdevis Y. Rodriguez-Caturla; Larissa P. Margalho; Juliana S. Graça; Arthur K.R. Pia; Viny L. Xavier; Melline F. Noronha; Lucélia Cabral; Wilson J.F. Lemos-Junior; Carmen J.C. Castillo; Anderson S. SantˈAna (International Journal of Food Microbiology, 2025)

Exploring the effects of cellulose sources on silver reduction and the bacterial removal of nanocellulose-based hydrogel beads - Diego Gomez-Maldonado; Brieanne R. Dickson; Gabriel Au; Michael J. Bortner; Mi Li; Eduardo Espinosa; Alejandro Rodriguez; Brendan Higgins; Maria S. Peresin (Carbohydrate Polymers, 2025)

Focal pharmacological manipulation of serotonin signaling in the amygdala does not alter social behavior - Jessica T. Jacobs; Rafael S. Maior; Hannah F. Waguespack; Carolina Campos-Rodriguez; Ludise Malkova; Patrick A. Forcelli (Psychopharmacology, 2025)

A review of the venom microbiome and its utility in ecology and evolution including future directions for emerging research - Marina E. De León; Eduardo G. P. Fox; Sara Dunaj; Ronald A. Jenner; Carl N. Keiser; Jason Macrander; Samantha A. Nixon; Clarissa J. Nobile; Daniel Petras; Eduardo Rodriguez-Roman; Anthony J. Saviola; Steven A. Trim; et al. (Symbiosis, 2025)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Sublethal effects of microplastic and oil co-exposure on biological rates and lipid profiles of keystone Arctic copepods - R. Almeda; R. Rodriguez-Torres; S. Rist; M. Winding; S. Jonasdottir; T. Gissel Nielsen (Environmental Pollution, 2024)

Air quality in olive mill wastewater evaporation ponds: Assessment of chemical and microbiological pollutants - G. Viteri; A. Rodríguez; A. Aranda; Y. Díaz de Mera; D. Rodríguez; N. Rodriguez-Fariñas; N. Valiente; G. Belinchón; S. Seseña (Environmental Pollution, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Diastereomers of the Anticancer Peptide CIGB-300 with Altered β-Turn Structures - Celia G. Moya; Rafael Rodriguez; Carlos S. Perez; Hilda Garay; Julian Wiesent; Stefan Gröger; Yordanka Masforrol; Yasser Perera; Silvio E. Perea; Jochen Balbach (International Journal of Peptide Research and Therapeutics, 2024)
Purpose The next-generation anti-tumor drug peptide CIGB-300, developed by the Center for Genetic Engineering and Biotechnology (CIGB), targets casein kinase 2 (CK2) and its substrates, implicating significant therapeutic potential in cancer treatment. A key focus of this study was to compare CIGB-300 and a primary synthetic byproduct, CIGB-300iso, which shares the amino acid sequence with CIGB-300 but was proposed to differ due to racemization. Methods This study explores the synthesis, characterization, and structural elucidation of CIGB-300 and its isomer CIGB-300iso by a comprehensive NMR analysis of seven synthesized diastereomers including amino acid residues C15, H21, and C25. Results This study revealed that CIGB-300iso contains one D enantiomer at position H21. The structures of both isoforms derived from NMR constraints disclosed that the L and D enantiomers have an altered peptide supersecondary structure, with a β-turn type IV 3 found in CIGB-300 and a type I β-turn in CIGB-300iso. Conclusion The configuration of H21 significantly impacts the peptide’s conformations, sidechain orientations and, potentially, its biological activity. These findings highlight the importance of enantiomerically pure peptides for the design and synthesis of drug peptides.

Unraveling autonomic cardiovascular control complexity during orthostatic stress: Insights from a mathematical model - Martin Miranda Hurtado; Rafael Kaempfer; Justen R. Geddes; Mette S. Olufsen; Maria Rodriguez-Fernandez (Mathematical Biosciences, 2024)

Authentication of grated hard cheeses and quantification of adulteration by FT-NIR spectroscopy and multivariate analysis - Lucas G. Visconti; Paulo Henrique Gonçalves Dias Diniz; David Douglas de Sousa Fernandes; María S. Rodriguez; Carolina V. Di Anibal (International Dairy Journal, 2024)

Association of pesticide exposure with respiratory health outcomes and rhinitis in avocado farmworkers from Michoacán, Mexico - Cecilia S. Alcalá; Cynthia Armendáriz-Arnez; Ana M. Mora; Maria G. Rodriguez-Zamora; Asa Bradman; Samuel Fuhrimann; Christian Lindh; María José Rosa (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Integrating high-resolution remote sensing and empirical wildlife detection data for climate-resilient corridors across tropical elevational gradients - Ian M. McCullough; Christopher Beirne; Carolina Soto-Navarro; Amy Eppert; Eleanor Flatt; Yvonne J.M. Kemp; Péter K. Molnár; Michael S. Mooring; Yana Nikolova; Erik R. Olson; Carolina Pinto; Junior Porras; et al. (Biological Conservation, 2024)

The presence of two distinct mitochondrial lineages in the bottlenose dolphin (Tursiops truncatus) in Puerto Rico and their affinities with previously reported lineages - Grisel Rodriguez-Ferrer; Richard S. Appeldoorn; Antonio A. Mignucci-Giannoni; Renaldo Rinaldi; Nikolaos V. Schizas (Mammalian Biology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

What's that smell? The putrid scent of Rafflesia consueloae, its origin and developmental regulation - Erika Marie A. Bascos; Edwino S. Fernando; Melizar V. Duya; Lillian Jennifer V. Rodriguez (Flora, 2024)

A multi-technique approach to unveil the composition and fabrication of a pre-Roman glass masterpiece: a double-faced human-head shape polychrome glass pendant (2nd -1st c. BC) - S. Barroso-Solares; E. Estalayo; J. Aramendia; E. Rodriguez-Gutierrez; C. Sanz-Minguez; A. C. Prieto; J. M. Madariaga; J. Pinto (Archaeological and Anthropological Sciences, 2024)
Pre-Roman glass craftsmanship reached its summit with the development of complex polychrome glass beads, being the Phoenician glass pendants the most exquisite and elaborate example. The uniqueness and complexity of such findings could reveal key information for the understanding of the production and trade of glass pieces at that age. However, these findings have practically never been studied from a physic-chemical perspective. In this work, a remarkable polychrome glass pendant (2nd -1st c. BC) found at the archaeological site of Pintia (Padilla de Duero, Valladolid, Spain) is studied by a multi-analytical non-destructive approach, employing X-ray tomography to understand its fabrication procedure, as well as X-ray fluorescence (XRF) and Raman spectroscopy, both employed in microscopic mode, to determine the composition of each glass employed in its fabrication. The outstanding preservation state and well-defined archaeological context of this glass pendant offered a unique opportunity to expand the understanding of pre-Roman glass pieces, while the combination of the experimental techniques employed provided the first complete and detailed study of a Phoenician glass pendant. The fabrication procedure of the pendant has been identified step-by-step, showing evidence of the use of pre-made pieces for the eyes, as well as hints of its fabrication in a secondary workshop. Moreover, the microchemical analysis of the vividly colored glasses by XRF and Raman spectroscopy revealed a composition compatible with the use of natron as fluxing agent, typical of Phoenician glass, the presence of surface alterations corresponding to carbonatation processes, as well as the nature of the employed chromophores or pigments: Mn, Cu, and Co for the blue, Fe-S for the black, CaSb 2 O 7 and CaSb 2 O 7 + TiO 2 for two diverse white glasses, and a pyrochloric triple oxide (Pb 2 Sb 2 − x Sn x O 7−x/2 ) and lead oxides for the yellow. Remarkably, the use of pyrochloric triple oxides as yellow pigments has scarcely been previously reported at that age. Finally, the identification by Raman spectroscopy of CaSb 2 O 7 and the β-phase of CaSiO 3 , as well as the Raman spectra features of the glass matrix corresponding to the blue glass, indicated maximum firing temperatures below 1100 °C.

No Effect of Breakfast Consumption Observed for Afternoon Resistance Training Performance in Habitual Breakfast Consumers and Nonconsumers: A Randomized Crossover Trial - Matthew T. Stratton; Madelin R. Siedler; Christian Rodriguez; Patrick S. Harty; Jake R. Boykin; Dale S. Keith; Jacob J. Green; Sarah J. White; Ethan Tinoco; Brielle DeHaven; Trisha A. VanDusseldorp; Grant M. Tinsley (Journal of the Academy of Nutrition and Dietetics, 2024)

Hydroclimate variability in the Tropical Andes recorded by δ18O isotopes from a new network of Polylepis tarapacana tree-rings - Claudio Álvarez; Duncan A. Christie; Álvaro González-Reyes; Thomas T. Veblen; Gerhard Helle; Carlos LeQuesne; Milagros Rodriguez-Caton; Paul Szejner; Felipe Flores-Sáez; Tania Gipoulou-Zúñiga; Manuel Suazo-Álvarez; Tomás Muñoz-Salazar; et al. (Global and Planetary Change, 2024)

Impact of a water restriction on the summer climatic benefits of trees inside an outdoor street canyon scale model - J. Thierry; S. Herpin; R. Levi; D. Canonne; S. Demotes-Mainard; P. Cannavo; D. Lemesle; L. Brialix; F. Rodriguez; P.E. Bournet (Building and Environment, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Lightning-induced fire regime in Portugal based on satellite-derived and in situ data - Lucas S. Menezes; Ana Russo; Renata Libonati; Ricardo M. Trigo; José M.C. Pereira; Akli Benali; Alexandre M. Ramos; Célia M. Gouveia; Carlos A. Morales Rodriguez; Ricardo Deus (Agricultural and Forest Meteorology, 2024)

The history and processes of Titan's equator from the geospatial-topology of spectrally distinct units - N. Kutsop; A.G. Hayes; C. Sotin; J.I. Lunine; S.P.D. Birch; P.M. Corlies; K. Lawrence; S. Le Mouélic; J. Madden; M.J. Malaska; S. Rodriguez; J.M. Soderblom; et al. (Icarus, 2024)

Pioneering minimum liquid discharge desalination: A pilot study in Lampedusa Island - C. Morgante; F. Vassallo; C. Cassaro; G. Virruso; D. Diamantidou; N. Van Linden; A. Trezzi; C. Xenogianni; R. Ktori; M. Rodriguez; G. Scelfo; S. Randazzo; et al. (Desalination, 2024)

Calcium-based catalyst prepared in the presence of biopolymer/biomass for biodiesel production: Elucidating their influence on the catalytic efficiency - Yuliana Rodriguez; Sebastian Ponce; Mateus H. Keller; Karla Vizuete; Alexis Debut; Bruno S. Souza; José R. Mora (Biomass and Bioenergy, 2024)

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

Evaluation of imidacloprid (Confidor OD®) genotoxicity in Chrysoperla externa eggs (Neuroptera: Chrysopidae) through comet assay - Fernández Acevedo V; Rodriguez Gil S; Seoane A; Minardi G; M.I. Schneider (Chemosphere, 2024)

Like noodles in a soup: Anthropogenic microfibers are being ingested by juvenile fish in nursery grounds of the Southwestern Atlantic Ocean - Nadia M. Alves; Julieta Rodriguez; Rosana Di Mauro; Julieta S. Rodríguez; David Maldonado; Mara S. Braverman; Brenda Temperoni; Marina V. Diaz (Marine Pollution Bulletin, 2024)

Enabling particle transport on CAD-based geometries for radiation simulations with penRed - S. Oliver; S. Rodriguez Bosca; V. Giménez-Alventosa (Computer Physics Communications, 2024)

Exploring genomic inbreeding and selection signatures in a commercial Brangus herd through functional annotation - Gabriel A. Zayas; Eduardo E. Rodriguez; Aakilah S. Hernandez; Fernanda M. Rezende; Raluca G. Mateescu (Journal of Applied Genetics, 2024)

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Pathological and transcript analysis of protection induced by MTBVAC and BCG against Mycobacterium tuberculosis infection in rhesus macaques - F.J. Salguero; J. Medley; L. Hunter; I. Ruedas-Torres; A. Bird; E. Puentes; E. Rodriguez; S.J. Waddell; C. Martin; S. Sharpe (Journal of Comparative Pathology, 2024)

Aluminum-based catalysts prepared in the presence of pectin for low-energy biodiesel production - Sebastian Ponce; Pablo A. Gangotena; Cahuenas Anthony; Yuliana Rodriguez; Heitor A.G. Bazani; Mateus H. Keller; Bruno S. Souza; Karla Vizuete; Alexis Debut; José R. Mora (Fuel, 2024)

Considerations for the development of guidance on dose level selection for developmental and reproductive toxicity studies - R.W. Lewis; A.K. Andrus; J. Arroyo; S. Brescia; P.A. Botham; M. Corvaro; G.P. Daston; T. Hofmann; C. Rodriguez; F. Sewell; B. van Ravenzwaay; K. Wiench; et al. (Regulatory Toxicology and Pharmacology, 2024)

New palynological record for the Puesto Albornoz Formation (Golfo San Jorge basin, Argentina): Stratigraphic and paleoenvironmental implications - Valeria S. Perez Loinaze; Magdalena Llorens; Agustín R. Rodriguez; José O. Allard; Nicolás Foix (Journal of South American Earth Sciences, 2024)

Possibly seismically triggered avalanches after the S1222a Marsquake and S1000a impact event - A. Lucas; I.J. Daubar; M. Le Teuff; C. Perrin; T. Kawamura; L. Posiolova; P. Lognonné; S. Rodriguez; D. Giardini; G. Sainton; A. Mangeney; A. McEwen (Icarus, 2024)

Human health and environmental risk assessment of metals in community gardens of Winnipeg, Manitoba, Canada - Teresa Senderewich; Doug Goltz; Jose Luis Rodriguez-Gil; Brian Laird; Ryan S. Prosser; Mark L. Hanson (Environmental Science and Pollution Research, 2024)

Geographical distribution of metals and metalloids along the estuary of the Oka River in the biosphere reserve of Urdaibai, Spain - X. Alberdi Igartua; A. Rodriguez-Iruretagoiena; A. Gredilla; S. Fdez-Ortiz de Vallejuelo; G. Arana; A. de Diego; J.M. Madariaga (Marine Pollution Bulletin, 2024)

Assessment of gill microbiome of two strains of Atlantic salmon reared in flowthrough and recirculation hatcheries and following seawater transfer - Petra R. Quezada-Rodriguez; Jamie Downes; Fintan Egan; Richard S. Taylor; Samantha White; Aisling Brenan; Megan L. Rigby; Barbara F. Nowak; James W. Wynne; Neil M. Ruane (Aquaculture, 2024)

High potential for Brassica tournefortii spread in North American introduced range, despite highly conserved niche - Clarissa S. Rodriguez; Miranda Brooke Rose; Santiago José Elías Velazco; Janet Franklin; Loralee Larios (Biological Invasions, 2024)

Current deformation along the northern Caribbean plate boundary from GNSS measurements in Cuba - E. Calais; O.F. Gonzalez; E.D. Arango-Arias; B. Moreno; R. Palau; M. Cutie; E. Diez; C. Montenegro; E. Rodriguez Roche; J. Garcia; E. Castellanos; S. Symithe (Tectonophysics, 2023)

Sustained Three-Year Declines in Forest Soil Respiration are Proportional to Disturbance Severity - Kayla C. Mathes; Stephanie Pennington; Carly Rodriguez; Ben Bond-Lamberty; Jeff W. Atkins; Christoph S. Vogel; Christopher M. Gough (Ecosystems, 2023)

Shelf life estimation of refrigerated vacuum packed beef accounting for uncertainty - Magdevis Y. Rodriguez-Caturla; Alberto Garre; Carmen Josefina Contreras Castillo; Marcel H. Zwietering; Heidy M.W. den Besten; Anderson S. SantˈAna (International Journal of Food Microbiology, 2023)

Financial and Operational Feasibility Pilot of a Medically Tailored Meal Program - W. Phillips; S. Geneva; M. Yepes-Rios; M. Alejandro-Rodriguez; J. Evans; R. Miles (Journal of the Academy of Nutrition and Dietetics, 2023)

First evidence of environmental bioaccumulation of pharmaceuticals on adult native anurans (Rhinella arenarum) from Argentina - C. Salgado Costa; F. Bahl; G.S. Natale; T.M. Mac Loughlin; D.J.G. Marino; A. Venturino; S. Rodriguez-Mozaz; L.H.M.L.M. Santos (Environmental Pollution, 2023)

Kinetics of Na- and K- uranyl arsenate dissolution - Isabel Meza; Noah Jemison; Jorge Gonzalez-Estrella; Peter C. Burns; Virginia Rodriguez; Ginger E. Sigmon; Jennifer E.S. Szymanowski; Abdul-Mehdi S. Ali; Kaelin Gagnon; José M. Cerrato; Peter Lichtner (Chemical Geology, 2023)

Cu(II)-acylhydrazone complex, a potent and selective antitumor agent against human osteosarcoma: Mechanism of action studies over in vitro and in vivo models - Lucia M. Balsa; Luisina M. Solernó; Maria R. Rodriguez; Beatriz S. Parajón-Costa; Ana C. Gonzalez-Baró; Daniel F. Alonso; Juan Garona; Ignacio E. León (Chemico-Biological Interactions, 2023)

Induction of proteasomal activity in mammalian cells by lifespan-extending tRNA synthetase inhibitors - Blaise L. Mariner; Antonio S. Rodriguez; Olivia C. Heath; Mark A. McCormick (GeroScience, 2023)
We have recently shown that multiple tRNA synthetase inhibitors can greatly increase lifespan in multiple models by acting through the conserved transcription factor ATF4. Here, we show that these compounds, and several others of the same class, can greatly upregulate mammalian ATF4 in cells in vitro, in a dose dependent manner. Further, RNASeq analysis of these cells pointed toward changes in protein turnover. In subsequent experiments here we show that multiple tRNA synthetase inhibitors can greatly upregulate activity of the ubiquitin proteasome system (UPS) in cells in an ATF4-dependent manner. The UPS plays an important role in the turnover of many damaged or dysfunctional proteins in an organism. Increasing UPS activity has been shown to enhance the survival of Huntington’s disease cell models, but there are few known pharmacological enhancers of the UPS. Additionally, we see separate ATF4 dependent upregulation of macroautophagy upon treatment with tRNA synthetase inhibitors. Protein degradation is an essential cellular process linked to many important human diseases of aging such as Alzheimer’s disease and Huntington’s disease. These drugs’ ability to enhance proteostasis more broadly could have wide-ranging implications in the treatment of important age-related neurodegenerative diseases.

P24-14: Development of a semi-quantitative tool to determine absorption factors during toxicokinetic evaluation of chemicals under REACH - S. Bergeret; Y. Pareja Rodriguez; I. Van de Gevel; S. Jacobs (Toxicology Letters, 2023)

S01-03: PFAS exposure among European teenagers included in the HBM4EU-Aligned studies and its relationship with reproductive hormone and Kisspeptin levels - M.F. Fernández; A. Rodriguez-Carrillo; S. Pedraza; E. den Hond; L. Fábelová; S. Remy; G. Schoeters (Toxicology Letters, 2023)

Interlaboratory study: Testing reproducibility of solid biofuels component identification using reflected light microscopy - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Tushar Adsul; Neža Malenšek Andolšek; Omid Haeri Ardakani; Tara Congo; Batbold Demberelsuren; Bryon S. Donohoe; Ashley Douds; Deolinda Flores; et al. (International Journal of Coal Geology, 2023)

Influence of loading rates and feeding conditions on hybrid constructed wetlands integrated with microbial fuel cells - Gustavo S. Colares; Naira Dell'Osbel; Igor Conrad; Gabriele Paranhos; Sabrina B. Vaz; Gislayne Oliveira; Letícia Mesacasa; Deison Fochi; Odorico Konrad; Lucia R. Rodrigues; Carlos A. Lutterbeck; Adriane Lawisch Rodriguez; et al. (Ecological Engineering, 2023)

Coastal raptors and raiders: New bird tracks in the Pleistocene of SW iberian Peninsula - Carlos Neto de Carvalho; João Belo; Silvério Figueiredo; Pedro P. Cunha; Fernando Muñiz; Zain Belaústegui; Mário Cachão; Joaquín Rodriguez-Vidal; Luis M. Cáceres; Andrea Baucon; Andrew S. Murray; Jan-Pieter Buylaert; et al. (Quaternary Science Reviews, 2023)

Correction to: Neuromuscular electrical stimulation in garments optimized for compliance - R. Juthberg; J. Flodin; L. Guo; S. Rodriguez; N. K. Persson; P. W. Ackermann (European Journal of Applied Physiology, 2023)

Neuromuscular electrical stimulation in garments optimized for compliance - R. Juthberg; J. Flodin; L. Guo; S. Rodriguez; N. K. Persson; P. W. Ackermann (European Journal of Applied Physiology, 2023)
Purpose Physical inactivity is associated with muscle atrophy and venous thromboembolism, which may be prevented by neuromuscular electrical stimulation (NMES). This study aimed to investigate the effect on discomfort, current amplitude and energy consumption when varying the frequency and phase duration of low-intensity NMES (LI-NMES) via a sock with knitting-integrated transverse textile electrodes (TTE). Methods On eleven healthy participants (four females), calf-NMES via a TTE sock was applied with increasing intensity (mA) until ankle-plantar flexion at which point outcomes were compared when testing frequencies 1, 3, 10 and 36 Hz and phase durations 75, 150, 200, 300 and 400 µs. Discomfort was assessed with a numerical rating scale (NRS, 0–10) and energy consumption was calculated and expressed in milli-Joule (mJ). Significance set to p ﻿≤ 0.05. Results 1 Hz yielded a median (inter-quartile range) NRS of 2.4 (1.0–3.4), significantly lower than both 3 Hz with NRS 2.8 (1.8–4.2), and 10 Hz with NRS 3.4 (1.4–5.4) (both p ≤ .014). Each increase in tested frequency resulted in significantly higher energy consumption, e.g. 0.6 mJ (0.5–0.8) for 1 Hz vs 14.9 mJ (12.3–21.2) for 36 Hz ( p = .003). Longer phase durations had no significant effect on discomfort despite generally requiring significantly lower current amplitudes. Phase durations 150, 200 and 400 µs required significantly lower energy consumption compared to 75 µs (all p ≤ .037). Conclusion LI-NMES applied via a TTE sock produces a relevant plantar flexion of the ankle with the best comfort and lowest energy consumption using 1 Hz and phase durations 150, 200 or 400 µs.

Evaluation of reference genes for qRT-PCR studies in the colchicine producing Gloriosa superba L. - Nekha Johnson; Diana Rodriguez Diaz; Sivakumar Ganapathy; John S. Bass; Toni M. Kutchan; Abdul L. Khan; Albert B. Flavier (Plant Biotechnology Reports, 2023)

Metals and metalloids in high-altitude Pyrenean lakes: sources and distribution in pre-industrial and modern sediments - Azibar Rodriguez-Iruretagoiena; Ainara Gredilla; Silvia Fdez-Ortiz de Vallejuelo; Gorka Arana; Maite Meaurio; Juan Manuel Madariaga; Jean Christophe Auguet; Aridane González González; Oleg S. Pokrovsky; Luis Camarero; Alberto de Diego (Environmental Science and Pollution Research, 2023)
High-altitude Pyrenean lakes are ecosystems far from local pollution sources, and thus they are particularly sensitive to the atmospheric deposition of metals and metalloids. This study aims to quantify the effect of human activity in 18 lakes located in both side of the France–Spain frontier. Sediment cores were collected in summer 2013, sampled at a 1cm resolution and the concentration of 24 elements was measured by ICP-MS. Statistic and chemometric analysis of the results highlights the influence of the geographical position and lithogenic features of each lake basin on trapping pollutants. More than the 80% of the lakes showed values of enrichment factor (EF) above 2 for at least one of the elements investigated in at least one core interval, which corroborates the existence of historical anthropogenic inputs of elements in the studied area. The results demonstrate the natural origin of As and Ti in Pyrenees, together with the significant anthropogenic inputs of Cd, Pb, Sb and Sn from ancient times. The data set points mining activities as the main historical source of pollution and illustrate the large impact of the industrial revolution. The regional variability could reflect also differential long-range transport, followed by dry or wet deposition.

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Contribution of TGFß and of a cocktail of TGFß and the pro-inflammatory cytokines IL-1, IL- 6 and TNFα to the establishment of a fibrotic phenotype in endometrial fibroblasts of mares - Yat S. Wong; Pamela Poblete; Lidice Mendez; Ana C. Mancanares; Lleretny Rodriguez-Alvarez; Fernando E. Saravia; Fidel O. Castro (Journal of Equine Veterinary Science, 2023)

Metronidazole photodegradation under solar light with UiO-66-NH2 photocatalyst: Mechanisms, pathway, and toxicity assessment - Y.-L. Wang; A. Gómez-Avilés; S. Zhang; J.J. Rodriguez; J. Bedia; C. Belver (Journal of Environmental Chemical Engineering, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

A case of feline osteochondromatosis - Á. Gómez; A. Rodriguez Largo; E. Pérez; P. Mendivil; S. Loomans; M. Pérez; K. Chiers; L. Luján (Journal of Comparative Pathology, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

Genus and size-specific susceptibility of soft corals to 2020 bleaching event in the Philippines - Christine C. Baran; Rhea Mae A. Luciano; Christine S. Segumalian; Darryl Anthony M. Valino; Maria Vanessa Baria-Rodriguez (Marine Biology Research, 2023)

Bovine embryos release extracellular vesicles with differential miRNA signature during the compaction and blastulation stages - Bárbara Melo-Báez; Edwin A. Mellisho; Yat S. Wong; Joel Cabezas; Diego Caamaño; Constanza Aguilera; Gonzalo Riadi; Fidel O. Castro; Lleretny Rodriguez-Alvarez (Reproductive Biology, 2023)

Holistic Assessment of Calcium Fertilization in Potato: Diagnostic, Productivity, and Tuber Quality - C. M. Giletto; M. Kloster Erreguerrena; P. Ceroli; W. Carciochi; S. E. Silva; S. Rodriguez; F. Salvagiotti; N. I. Reussi Calvo (Journal of Soil Science and Plant Nutrition, 2023)

The impacts of social determinants of health and cardiometabolic factors on cognitive and functional aging in Colombian underserved populations - Hernando Santamaria-Garcia; Sebastian Moguilner; Odir Antonio Rodriguez-Villagra; Felipe Botero-Rodriguez; Stefanie Danielle Pina-Escudero; Gary O’Donovan; Cecilia Albala; Diana Matallana; Michael Schulte; Andrea Slachevsky; Jennifer S. Yokoyama; Katherine Possin; et al. (GeroScience, 2023)
Global initiatives call for further understanding of the impact of inequity on aging across underserved populations. Previous research in low- and middle-income countries (LMICs) presents limitations in assessing combined sources of inequity and outcomes (i.e., cognition and functionality). In this study, we assessed how social determinants of health (SDH), cardiometabolic factors (CMFs), and other medical/social factors predict cognition and functionality in an aging Colombian population. We ran a cross-sectional study that combined theory- (structural equation models) and data-driven (machine learning) approaches in a population-based study ( N = 23,694; M = 69.8 years) to assess the best predictors of cognition and functionality. We found that a combination of SDH and CMF accurately predicted cognition and functionality, although SDH was the stronger predictor. Cognition was predicted with the highest accuracy by SDH, followed by demographics, CMF, and other factors. A combination of SDH, age, CMF, and additional physical/psychological factors were the best predictors of functional status. Results highlight the role of inequity in predicting brain health and advancing solutions to reduce the cognitive and functional decline in LMICs.

Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine - Daniel R. Rosell; Mark Slifstein; Judy Thompson; Xiaoyan Xu; M. Mercedes Perez-Rodriguez; Margaret M. McClure; Erin A. Hazlett; Antonia S. New; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; Larry S. Siever; et al. (Psychopharmacology, 2023)

Integrating phytoplankton pigment and DNA meta‐barcoding observations to determine phytoplankton composition in the coastal ocean - Dylan Catlett; David A. Siegel; Paul G. Matson; Emma K. Wear; Craig A. Carlson; Thomas S. Lankiewicz; M. Debora Iglesias‐Rodriguez (Limnology and Oceanography, 2023)
Quantifying phytoplankton composition is critical to predicting marine ecosystem structure and function. DNA meta‐barcoding and high‐performance liquid chromatography (HPLC) pigment analysis are two widely used methods for assessing phytoplankton composition; however, comparing their performance has been done only rarely. Here, we integrate DNA meta‐barcoding and HPLC pigment observations to determine eukaryotic phytoplankton composition in the Santa Barbara Channel, California. We find that both methods identify the same four dominant eukaryotic phytoplankton taxa (diatoms, dinoflagellates, chlorophytes, and prymnesiophytes), but inter‐ and intra‐lineage variability in biomarker pigmentation (associated with both a lack of taxonomic specificity of biomarker pigments and intrinsic differences in accessory pigmentation) drives substantial disagreement between the methods. Covariation network analysis circumvents this disagreement and reveals that diverse assemblages of phytoplankton and other protists covary with distinct suites of biomarker pigments. Our results highlight the strengths and weaknesses of each method in characterizing phytoplankton composition and reveal novel insights into phytoplankton physiology that could only be gained by integrating the two methods. Finally, we suggest a path to monitor eukaryotic plankton communities on unprecedented spatiotemporal scales based on the covariation of unique phytoplankton and protistan assemblages with remotely sensible phytoplankton pigment concentrations.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

PFAS levels and determinants of variability in exposure in European teenagers – Results from the HBM4EU aligned studies (2014–2021) - D. Richterová; E. Govarts; L. Fábelová; K. Rausová; L. Rodriguez Martin; L. Gilles; S. Remy; A. Colles; L. Rambaud; M. Riou; C. Gabriel; D. Sarigiannis; et al. (International Journal of Hygiene and Environmental Health, 2023)

The role of copper crystallization and segregation toward enhanced methanol synthesis via CO2 hydrogenation over CuZrO2 catalysts: A combined experimental and computational study - Francielle C.F. Marcos; Raphael S. Alvim; Lili Lin; Luis E. Betancourt; Davi D. Petrolini; Sanjaya D. Senanayake; Rita M.B. Alves; José M. Assaf; Jose A. Rodriguez; Reinaldo Giudici; Elisabete M. Assaf (Chemical Engineering Journal, 2023)

Prevalence of epitheliocystis in freshwater Atlantic salmon reared in flow‐through and recirculation aquaculture systems - Petra R. Quezada‐Rodriguez; Richard S. Taylor; Jamie Downes; Fintan Egan; Samantha White; Aisling Brenan; Megan Rigby; Barbara F. Nowak; Neil M. Ruane; James W. Wynne (Journal of Fish Diseases, 2022)
Epitheliocystis, an intracellular bacterial infection in the gills and skin epithelium, has been frequently reported in Atlantic salmon ( Salmo salar ) during freshwater production in a number of countries. This study describes the prevalence and intensity of a natural epitheliocystis infection present in the gills of two strains of Atlantic salmon reared in either a flow‐through (FT) or a recirculation aquaculture system (RAS) in Ireland. Repeated sampling of gills prior to and throughout seawater transfer, histology and quantitative real‐time PCR were used to determine infection prevalence and intensity. Despite no clinical gill disease, and minor histopathological changes, epitheliocystis lesions were identified in histology at all time points. Specific PCR confirmed the presence of Candidatus Clavichlamydia salmonicola in both strains and its number of copies was correlated with intensity of epitheliocystis lesions. A significant interaction between hatchery system and fish strain on the prevalence and intensity of gill epitheliocystis was found both using histological and molecular methods. Specifically, fish from FT had higher prevalence and intensity than RAS reared fish and within FT, the Irish cohort were more affected than Icelandic.

Movement and mortality of invasive suckermouth armored catfish during a spearfishing control experiment - Allison Hay; Christopher L. Riggins; Thomas Heard; Collin Garoutte; Yeyetzi Rodriguez; Francesca Fillipone; Kristy K. Smith; Nick Menchaca; Janaye Williamson; Joshuah S. Perkin (Biological Invasions, 2022)

Epimutation in inherited metabolic disorders: the influence of aberrant transcription in adjacent genes - Jean-Louis Guéant; Youssef Siblini; Céline Chéry; Guillaume Schmitt; Rosa-Maria Guéant-Rodriguez; David Coelho; David Watkins; David S. Rosenblatt; Abderrahim Oussalah (Human Genetics, 2022)

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

Enacting boundaries or building bridges? Language and engagement in food-energy-water systems science - Valoree S. Gagnon; Chelsea Schelly; William Lytle; Andrew Kliskey; Virginia H. Dale; Anna-Maria Marshall; Luis F. Rodriguez; Paula Williams; Michael Waasegiizhig Price; Elizabeth A. Redd; Margaret A. Noodin (Socio-Ecological Practice Research, 2022)
Scientific study of issues at the nexus of food–energy–water systems (FEWS) requires grappling with multifaceted, “wicked” problems. FEWS involve interactions occurring directly and indirectly across complex and overlapping spatial and temporal scales; they are also imbued with diverse and sometimes conflicting meanings for the human and more-than-human beings that live within them. In this paper, we consider the role of language in the dynamics of boundary work, recognizing that the language often used in stakeholder and community engagement intended to address FEWS science and decision-making constructs boundaries and limits diverse and inclusive participation. In contrast, some language systems provide opportunities to build bridges rather than boundaries in engagement. Based on our experiences with engagement in FEWS science and with Indigenous knowledges and languages, we consider examples of the role of language in reflecting worldviews, values, practices, and interactions in FEWS science and engagement. We particularly focus on Indigenous knowledges from Anishinaabe and the language of Anishinaabemowin, contrasting languages of boundaries and bridges through concrete examples. These examples are used to unpack the argument of this work, which is that scientific research aiming to engage FEWS issues in working landscapes requires grappling with embedded, practical understandings. This perspective demonstrates the importance of grappling with the role of language in creating boundaries or bridges, while recognizing that training in engagement may not critically reflect on the role of language in limiting diversity and inclusivity in engagement efforts. Leaving this reflexive consideration of language unexamined may unknowingly perpetuate boundaries rather than building bridges, thus limiting the effectiveness of engagement that is intended to address wicked problems in working landscapes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of action observation on muscle strength/weakness and corticospinal excitability in older adults - Kylie K. Harmon; Ryan M. Girts; Jason I. Pagan; Gabriela Rodriguez; Matt S. Stock (Experimental Brain Research, 2022)

Experimental and Computational Models of Transport of Galectin-3 Through Glycosylated Matrix - Janny Piñeiro-Llanes; Camille D. Rodriguez; Shaheen A. Farhadi; Gregory A. Hudalla; Malisa Sarntinoranont; Chelsey S. Simmons (Annals of Biomedical Engineering, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Cell death induced by fumonisin B1 in two maize hybrids: correlation with oxidative status biomarkers and salicylic and jasmonic acids imbalances - Santiago N. Otaiza-González; Verónica S. Mary; Silvina L. Arias; Lidwina Bertrand; Pilar A. Velez; María G. Rodriguez; Héctor R. Rubinstein; Martín G. Theumer (European Journal of Plant Pathology, 2022)

Revealing diagnostic characters through morphological evolution in cleptoparasitic spider wasps (Hymenoptera, Pompilidae, Ceropales ) - Cecilia Waichert; Juanita Rodriguez; Arkady S. Lelej; Carol D. von Dohlen; James P. Pitts (Zoologica Scripta, 2022)
Spider wasps (Hymenoptera: Pompilidae) cleptoparasites, such as Ceropales Latreille, have evolved the ability to steal the spiders from other pompilids. This behaviour is often observed with morphological adaptations that might mislead taxonomic decisions due to convergence. For instance, four subgenera, Bifidoceropales Wolf, Ceropales s. str., Hemiceropales Wolf and Priesnerius Móczár and six species‐groups are recognized within Ceropales ; all with doubtful identification. We studied species of Ceropales in light of molecular and morphological characters to delimit lineages and to test the applicability of morphological traits in diagnosing them. We used the molecular nuclear markers long‐wavelength rhodopsin and 28S ribosomal RNA, and the mitochondrial Cytochrome C Oxidase I available at Genebank to reconstruct Bayesian and maximum likelihood phylogenetic trees. Our results disagree with the current subgeneric classification. We found that fore wing venation and the shape of the female posterior metasomal segments are key characters to differentiate lineages. We discuss morphological evolution of the sting apparatus using ancestral state reconstructions; and we propose Bifidoceropales as a junior subjective synonym of Ceropales s. str., whereas Priesnerius , stat. resurr. and Hemiceropales are redefined based on male and female morphological traits. This study raises important concerns, from the validity of diagnostic characters currently used to identify cleptoparasite spider wasps—and taxa with habitat constraints leading to homoplasies. Taxonomy can benefit from the reconstruction of ancestral traits by revealing reliable diagnostic characters. Moreover, our investigation provides a framework for evolutionary studies on hymenopteran cleptoparasitoids and sets the basis for future phylogenomic investigations on Ceropales by opening new perspectives for taxonomic acts and guiding taxonomic sampling efforts.

Two Fish in a Pod. Mislabelling on Board Threatens Sustainability in Mixed Fisheries - Carmen Blanco-Fernandez; Karim Erzini; Sara Rodriguez-Diego; Pablo Alba-Gonzalez; Ndiaga Thiam; Fambaye Ngom Sow; Mamadou Diallo; Jónas R. Viðarsson; Duarte Fernández-Vidal; Jorge M. S. Gonçalves; Mafalda Rangel; Kim Stobberup; et al. (Frontiers in Marine Science, 2022)
Accuracy in reporting captures is a key element to achieve fisheries sustainability. However, identification of the catches might be a challenge when two or more species are morphologically similar and caught jointly, like the mixed fisheries of black hakes in East Atlantic African waters. Black hakes ( Merluccius senegalensis and M. polli ) are tough to differentiate without previous training due to their high morphological resemblance. The two species are managed as a single stock, although the biological differences between them suggest the need of a separate management. In this study, a total of 806 black hakes were visually identified by fishers on deck of fishing vessels operating in Mauritania and Senegal waters, then assigned to a species by sequencing 450bp of the Mitochondrial Control Region. Comparing the results with visual identification we found 31.4% of the total catch were incorrectly labelled on board by the fishermen. The accuracy of the fishers’ identification depended on the depth of capture and on fish size, larger individuals caught from deeper waters being more correctly assigned to M. polli . Mislabelling biased to M. polli suggests that M . senegalensis , already catalogued as endangered, is being underreported, which could endanger the conservation of this species and threaten the sustainability of black hake fisheries. Our results highlight the need for separate evaluation of the stocks in mixed fisheries for morphologically similar fish. Thus, monitoring through DNA barcoding in the very first step of the seafood chain surveys would improve accurate species delimitation and reduce its impact on the correct assessment of the stocks.

Mesenchymal Stromal Cell‐derived Extracellular Vesicles in Preclinical Animal Models of Tumor Growth: Systematic Review and Meta‐analysis - Adrian J.M. Bailey; Alvin Tieu; Manika Gupta; Mitchell Slobodian; Risa Shorr; Tim Ramsay; Rosendo A. Rodriguez; Dean A. Fergusson; Manoj M. Lalu; David S. Allan (Stem Cell Reviews and Reports, 2022)

“Right diet for the right person”: a focus group study of nutritionist-dietitians’ perspectives on nutritional genomics and gene-based nutrition advice - Jacus S. Nacis; Marilou R. Galang; Jason Paolo H. Labrador; Milflor S. Gonzales; Aurora Maria Francesca D. Dablo; Diana Glades A. Domalanta-Ronquillo; Victor Franco J. Alfonso; Idelia G. Glorioso; Marietta P. Rodriguez (Journal of Community Genetics, 2022)
Advances in nutritional genomics are intended to revolutionize nutrition practice. A basic understanding of nutritional genomics among nutritionist-dietitians is critical for such advancements to occur. As a precedent to the development and integration of gene-based nutrition advice, this study aimed to assess hospital-based nutritionist-dietitians’ perceptions of nutritional genomics. A total of ten focus group discussions (FGDs) with sixty-one registered nutritionist-dietitians (RNDs) from hospitals in the National Capital Region (NCR), Philippines, were conducted from October to November 2019. Data were collected using a pretested semistructured discussion guide, and thematic analysis was subsequently performed. Diverging perceptions about nutritional genomics were noted among the FGD participants. Five themes emerged relating to the enablers and barriers of gene-based nutrition advice: training and capacity building, the extent of information to be disclosed, cost, ethical considerations, and government support. Themes related to the desired features of the gene-based nutrition advice included being consent-driven, cost-effective, technology-oriented, and guided by standards. The results of this study suggest that training and continued learning will equip RNDs to provide nutrition advice based on genetic information. However, other factors, such as cost and ethical considerations, are critical dimensions that need to be acknowledged and addressed before integrating gene-based advice into nutrition practice.

Degradation of dibutyl phthalate by Paenarthrobacter sp. Shss isolated from Saravan landfill, Hyrcanian Forests, Iran - S. Shariati; C. Ebenau-Jehle; A. A. Pourbabaee; H. A. Alikhani; M. Rodriguez-Franco; M. Agne; M. Jacoby; R. Geiger; F. Shariati; M. Boll (Biodegradation, 2022)
Phthalic acid esters are predominantly used as plasticizers and are industrially produced on the million ton scale per year. They exhibit endocrine-disrupting, carcinogenic, teratogenic, and mutagenic effects on wildlife and humans. For this reason, biodegradation, the major process of phthalic acid ester elimination from the environment, is of global importance. Here, we studied bacterial phthalic acid ester degradation at Saravan landfill in Hyrcanian Forests, Iran, an active disposal site with 800 tons of solid waste input per day. A di- n -butyl phthalate degrading enrichment culture was established from which Paenarthrobacter sp. strain Shss was isolated. This strain efficiently degraded 1 g L –1 di- n -butyl phthalate within 15 h with a doubling time of 5 h. In addition, dimethyl phthalate, diethyl phthalate, mono butyl phthalate, and phthalic acid where degraded to CO 2 , whereas diethyl hexyl phthalate did not serve as a substrate. During the biodegradation of di- n -butyl phthalate, mono- n -butyl phthalate was identified in culture supernatants by ultra-performance liquid chromatography coupled to electrospray ionization quadrupole time-of-flight mass spectrometry. In vitro assays identified two cellular esterase activities that converted di- n -butyl phthalate to mono- n -butyl phthalate, and the latter to phthalic acid, respectively. Our findings identified Paenarthrobacter sp. Shss amongst the most efficient phthalic acid esters degrading bacteria known, that possibly plays an important role in di- n -butyl phthalate elimination at a highly phthalic acid esters contaminated landfill.

Spatial and Short-Term Temporal Patterns of Octocoral Assemblages in the West Philippine Sea - Jue Alef A. Lalas; Romina Therese S. Lim; Joey P. Cabasan; Christine S. Segumalian; Rhea Mae A. Luciano; Darryl Anthony M. Valino; Melchor R. Jacinto; Hazel O. Arceo; Maria Vanessa Baria-Rodriguez (Frontiers in Marine Science, 2022)
Octocorals are relatively understudied than other coral reef organisms despite their ecological and economic values. The Philippines is known to have high marine biodiversity, but information on octocorals is lacking. This study investigated spatial and temporal variations in the assemblage of octocorals in selected reef sites in the West Philippine Sea (WPS)- the Kalayaan Island Group (i.e., Pag-asa, Sabina, Lawak, and Northeast Investigator) and Ulugan in 2017 and 2019. Results showed high octocoral taxonomic richness (at least 10 families) in the study sites. Mean percent octocoral cover in WPS was 5.35% SE ± 0.55, with Sabina having the highest octocoral cover in both years. Significant differences in octocoral cover were observed among sites in both years, but among-station differences were only observed in 2017. Octocoral assemblage also differed among sites in both years (ANOSIM: R > 0.5, p < 0.05), wherein different octocoral taxa dominated in different sites. In particular, variations were driven by high cover of holaxonians, nephtheids, and coelogorgiids in Sabina, and clavulariids, tubiporiids, and xeniids in Northeast Investigator in 2017. In 2019, significant variations were driven by high cover of helioporiids in Pag-asa, while Sabina had higher abundance of holaxonians, nephtheids, alcyoniids, and xeniids. Short-term temporal variation on octocoral cover in monitoring stations in Pag-asa was not observed (Kruskal-Wallis, p > 0.05), although the overall mean octocoral cover increased from 1.23% ± SE 0.47 in 2017 to 2.09% SE ± 0.37 in 2019. Further, there was no significant change in the octocoral assemblage in Pag-asa between years (ANOSIM, R = 0.11, p = 0.07). This study highlights high octocoral taxonomic richness in the WPS relative to other sites in the Indo-Pacific Region and provides baseline information on the octocoral assemblages, which can be useful for future ecological studies and marine biodiversity conservation efforts.

Antidepressant activity of pharmacological and genetic deactivation of the small-conductance calcium-activated potassium channel subtype-3 - Mina G. Nashed; Shannon Waye; S. M. Nageeb Hasan; Diana Nguyen; Micaela Wiseman; Jing Zhang; Harry Lau; O. Chandani Dinesh; Roger Raymond; Iain R. Greig; Francis Rodriguez Bambico; José N. Nobrega (Psychopharmacology, 2022)

A Comprehensive, FAIR File Format for Neuroanatomical Structure Modeling - A. E. Sullivan; S. J. Tappan; P. J. Angstman; A. Rodriguez; G. C. Thomas; D. M. Hoppes; M. A. Abdul-Karim; M. L. Heal; Jack R. Glaser (Neuroinformatics, 2022)
With advances in microscopy and computer science, the technique of digitally reconstructing, modeling, and quantifying microscopic anatomies has become central to many fields of biological research. MBF Bioscience has chosen to openly document their digital reconstruction file format, the Neuromorphological File Specification, available at www.mbfbioscience.com/filespecification (Angstman et al., 2020). The format, created and maintained by MBF Bioscience, is broadly utilized by the neuroscience community. The data format’s structure and capabilities have evolved since its inception, with modifications made to keep pace with advancements in microscopy and the scientific questions raised by worldwide experts in the field. More recent modifications to the neuromorphological file format ensure it abides by the Findable, Accessible, Interoperable, and Reusable (FAIR) data principles promoted by the International Neuroinformatics Coordinating Facility (INCF; Wilkinson et al., Scientific Data, 3 , 160018,, 2016). The incorporated metadata make it easy to identify and repurpose these data types for downstream applications and investigation. This publication describes key elements of the file format and details their relevant structural advantages in an effort to encourage the reuse of these rich data files for alternative analysis or reproduction of derived conclusions.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Recognizing Indigenous peoples’ and local communities’ rights and agency in the post-2020 Biodiversity Agenda - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; Sara K. Diamond; David García-del-Amo; Sara Guadilla-Sáez; Natalia Hanazaki; Nicolas Kosoy; Margarita Lavides; Ana C. Luz; et al. (Ambio, 2022)
The Convention on Biological Diversity is defining the goals that will frame future global biodiversity policy in a context of rapid biodiversity decline and under pressure to make transformative change. Drawing on the work of Indigenous and non-Indigenous scholars, we argue that transformative change requires the foregrounding of Indigenous peoples’ and local communities’ rights and agency in biodiversity policy. We support this argument with four key points. First, Indigenous peoples and local communities hold knowledge essential for setting realistic and effective biodiversity targets that simultaneously improve local livelihoods. Second, Indigenous peoples’ conceptualizations of nature sustain and manifest CBD’s 2050 vision of “Living in harmony with nature.” Third, Indigenous peoples’ and local communities’ participation in biodiversity policy contributes to the recognition of human and Indigenous peoples’ rights. And fourth, engagement in biodiversity policy is essential for Indigenous peoples and local communities to be able to exercise their recognized rights to territories and resources.

NGS and phenotypic ontology-based approaches increase the diagnostic yield in syndromic retinal diseases - I. Perea-Romero; F. Blanco-Kelly; I. Sanchez-Navarro; I. Lorda-Sanchez; S. Tahsin-Swafiri; A. Avila-Fernandez; I. Martin-Merida; M. J. Trujillo-Tiebas; R. Lopez-Rodriguez; M. Rodriguez de Alba; I. F. Iancu; R. Romero; et al. (Human Genetics, 2021)
Syndromic retinal diseases (SRDs) are a group of complex inherited systemic disorders, with challenging molecular underpinnings and clinical management. Our main goal is to improve clinical and molecular SRDs diagnosis, by applying a structured phenotypic ontology and next-generation sequencing (NGS)-based pipelines. A prospective and retrospective cohort study was performed on 100 probands with an a priori diagnosis of non-Usher SRDs, using available clinical data, including Human Phenotype Ontology annotation, and further classification into seven clinical categories (ciliopathies, specific syndromes and five others). Retrospective molecular diagnosis was assessed using different molecular and bioinformatic methods depending on availability. Subsequently, uncharacterized probands were prospectively screened using other NGS approaches to extend the number of analyzed genes. After phenotypic classification, ciliopathies were the most common SRD (35%). A global characterization rate of 52% was obtained, with six cases incompletely characterized for a gene that partially explained the phenotype. An improved characterization rate was achieved addressing prospective cases (83%) and well-recognizable syndrome (62%) subgroups. The 27% of the fully characterized cases were reclassified into a different clinical category after identification of the disease-causing gene. Clinical-exome sequencing is the most appropriate first-tier approach for prospective cases, whereas whole-exome sequencing and bioinformatic reanalysis increases the diagnosis of uncharacterized retrospective cases to 45%, mostly those with unspecific symptoms. Our study describes a comprehensive approach to SRDs in daily clinical practice and the importance of thorough clinical assessment and selection of the most appropriate molecular test to be used to solve these complex cases and elucidate novel associations.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Beginnings of a plant parasite: early development of Rafflesia consueloae inside its Tetrastigma host - Erika Marie A. Bascos; Edwino S. Fernando; Melizar V. Duya; Lillian Jennifer V. Rodriguez (Planta, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Nutritional and ecotoxicological aspects of the acidotolerant alga Keratococcus rhaphidioides (Chlorophyta): a potential candidate for algal mediated bioremediation of extremely acidic waters - J. M. Cabrera; S. S. Schultz; G. D. Baffico; M. C. Rodriguez; F. L. Pedrozo; M. M. Diaz (Journal of Applied Phycology, 2021)

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Comparison of real and simulated lava flows in the Holocene volcanism of Gran Canaria (Canary Islands, Spain) with Q-LavHA: contribution to volcanic hazard management - A. Rodriguez-Gonzalez; M. Aulinas; S. Mossoux; F. J. Perez-Torrado; J. L. Fernandez-Turiel; M. Cabrera; C. Prieto-Torrell (Natural Hazards, 2021)

Correction to: Impact of acute high‑intensity interval exercise on plasma pentraxin 3 and endothelial function in obese individuals—a pilot study - Aaron L. Slusher; Brandon G. Fico; Katelyn M. Dodge; Ryan S. Garten; Peter J. Ferrandi; Alexandra A. Rodriguez; Gabriel Pena; Chun-Jung Huang (European Journal of Applied Physiology, 2021)

Impact of acute high-intensity interval exercise on plasma pentraxin 3 and endothelial function in obese individuals—a pilot study - Aaron L. Slusher; Brandon G. Fico; Katelyn M. Dodge; Ryan S. Garten; Peter J. Ferrandi; Alexandra A. Rodriguez; Gabriel Pena; Chun-Jung Huang (European Journal of Applied Physiology, 2021)

Managing groundwater supplies subject to drought: perspectives on current status and future priorities from England (UK) - M. J. Ascott; J. P. Bloomfield; I. Karapanos; C. R. Jackson; R. S. Ward; A. B. McBride; B. Dobson; N. Kieboom; I. P. Holman; A. F. Van Loon; E. J. Crane; B. Brauns; et al. (Hydrogeology Journal, 2021)
Effective management of groundwater resources during drought is essential. How is groundwater currently managed during droughts, and in the face of environmental change, what should be the future priorities? Four themes are explored, from the perspective of groundwater management in England (UK): (1) integration of drought definitions; (2) enhanced fundamental monitoring; (3) integrated modelling of groundwater in the water cycle; and (4) better information sharing. Whilst these themes are considered in the context of England, globally, they are relevant wherever groundwater is affected by drought.

Developing self-compatible diploid potato germplasm through recurrent selection - Maher Alsahlany; Felix Enciso-Rodriguez; Marco Lopez-Cruz; Joseph Coombs; David S. Douches (Euphytica, 2021)

Some like it, some do not: behavioral responses and central processing of olfactory–trigeminal mixture perception - Franziska S. Müschenich; Thorsten Sichtermann; Maria Elisa Di Francesco; Rea Rodriguez-Raecke; Lennart Heim; Marco Singer; Martin Wiesmann; Jessica Freiherr (Brain Structure and Function, 2021)
Exploring the potential of eucalyptol as a masking agent for aversive odors, we found that eucalyptol masks the olfactory but not the trigeminal sensation of ammonia in a previous study. Here, we further investigate the processing of a mixture consisting of eucalyptol and ammonia, two olfactory–trigeminal stimuli. We presented the two pure odors and a mixture thereof to 33 healthy participants. The nostrils were stimulated alternately (monorhinal application). We analyzed the behavioral ratings (intensity and pleasantness) and functional brain images. First, we replicated our previous finding that, within the mixture, the eucalyptol component suppressed the olfactory intensity of the ammonia component. Second, mixture pleasantness was rated differently by participants depending on which component dominated their mixture perception. Approximately half of the volunteers rated the eucalyptol component as more intense and evaluated the mixture as pleasant (pleasant group). The other half rated the ammonia component as more intense and evaluated the mixture as unpleasant (unpleasant group). Third, these individual differences were also found in functional imaging data. Contrasting the mixture either to eucalyptol or to both single odors, neural activation was found in the unpleasant group only. Activation in the anterior insula and SII was interpreted as evidence for an attentional shift towards the potentially threatening mixture component ammonia and for trigeminal enhancement. In addition to insula and SII, further regions of the pain matrix were involved when assessing all participant responses to the mixture. Both a painful sensation and an attentional shift towards the unpleasant mixture component complicates the development of an efficient mask because a pleasant perception is an important requirement for malodor coverage.

Superoxide-mediated oxidative stress accelerates skeletal muscle atrophy by synchronous activation of proteolytic systems - Young C. Jang; Karl Rodriguez; Michael S. Lustgarten; Florian L. Muller; Arunabh Bhattacharya; Anson Pierce; Jeongmoon J. Choi; Nan Hee Lee; Asish Chaudhuri; Arlan G. Richardson; Holly Van Remmen (GeroScience, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Lean on Your Land Grant: One University’s Approach to Address the Food Supply Chain Workforce during the COVID-19 Pandemic - S. Dee Jepsen; Lisa Pfeifer; Lyda G. Garcia; Zoë Plakias; Shoshanah Inwood; Joy N. Rumble; Mary T. Rodriguez; Judit E. Puskas; Samuel G. Custer (Journal of Agromedicine, 2020)

Dynamics of volatilomes emitted during cross-talking of plant-growth-promoting bacteria and the phytopathogen, Fusarium solani - A. Gutiérrez-Santa Ana; H. A. Carrillo-Cerda; J. Rodriguez-Campos; J. B. Velázquez-Fernández; O. A. Patrón-Soberano; S. M. Contreras-Ramos (World Journal of Microbiology and Biotechnology, 2020)

Role of Formulation Parameters on Intravitreal Dosing Accuracy Using 1 mL Hypodermic Syringes - Christian Weinmann; Ahmad S. Sediq; Martin Vogt; Hanns-Christian Mahler; Susanne Joerg; Sergio Rodriguez; Roman Mathaes; Dhananjay Jere (Pharmaceutical Research, 2020)

Enzymatic potential for the valorization of agro-industrial by-products - Mayara C. S. Barcelos; Cintia L. Ramos; Mohammed Kuddus; Susana Rodriguez-Couto; Neha Srivastava; Pramod W. Ramteke; Pradeep K. Mishra; Gustavo Molina (Biotechnology Letters, 2020)

Amphetamine-induced striatal dopamine release in schizotypal personality disorder - Judy L. Thompson; Daniel R. Rosell; Mark Slifstein; Xiaoyan Xu; Ethan G. Rothstein; Yosefa A. Modiano; Lawrence S. Kegeles; Harold W. Koenigsberg; Antonia S. New; Erin A. Hazlett; Margaret M. McClure; M. Mercedes Perez-Rodriguez; et al. (Psychopharmacology, 2020)

Mislocalization of SMN from the I-band and M-band in human skeletal myofibers in spinal muscular atrophy associates with primary structural alterations of the sarcomere - María T. Berciano; María S. Castillo-Iglesias; J. Fernando Val-Bernal; Vanesa Lafarga; José C. Rodriguez-Rey; Miguel Lafarga; Olga Tapia (Cell and Tissue Research, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Microbiome of the deep Lake Baikal, a unique oxic bathypelagic habitat - Pedro J. Cabello‐Yeves; Tamara I. Zemskaya; Alexandra S. Zakharenko; Mariya V. Sakirko; Vyacheslav G. Ivanov; Rohit Ghai; Francisco Rodriguez‐Valera (Limnology and Oceanography, 2020)
Lake Baikal is the deepest lake in the world. Its depth provides the only bathypelagic (> 1000 m deep) freshwater habitat on Earth and its oxic, ultra‐oligotrophic features make it a freshwater counterpart of the deep ocean. Here we have analyzed metagenomes from 1250 and 1350 m deep samples and built 231 metagenome‐assembled genomes (MAGs). We detected high fractions of Thaumarchaeota (ca. 20% of 16S rRNA reads) and members of the candidate phyla radiation (CPR) (3–4.5%). Among the MAGs, we obtained ammonia‐oxidizing archaea (AOA, Nitrosopumilaceae) and bacteria (AOB, Nitrosomonadaceae), and nitrite‐oxidizers (Nitrospirae) indicating very active nitrification. A new clade of freshwater SAR202 Chloroflexi and methanotrophs ( Methyloglobulus ) were also remarkably abundant, the latter reflecting a possible role of methane oxidation as well. Novel species of streamlined and cosmopolitan bacteria such as Ca. Fonsibacter or acI Actinobacteria were more abundant at the surface but also present in deep waters. Conversely, CPRs, Myxococcales, Chloroflexi, DPANN (Diapherotrites, Parvarchaeota, Aenigmarchaeota, Nanoarchaeota and Nanohaloarchaeota) archaea, or Gammaproteobacteria were found only in bathypelagic samples. We noted various important taxonomic and metabolic differences between deep aphotic region of Lake Baikal and marine waters of similar depth: Betaproteobacteriales, CPR, and DPANN superphylum were only found in bathypelagic Baikal, while Deltaproteobacteria, Gammaproteobacteria, or Alphaproteobacteria prevailed in oceanic samples. The genes mediating ammonia and methane oxidation, aromatic compound degradation, or alkane/methanesulfonate monooxygenases were detected in higher numbers in deep Baikal compared to their oceanic counterparts or its own surface. Overall, depth seems to be less relevant than salinity in configuring the microbial community.

Three-dimensional regional bi-ventricular shape remodeling is associated with exercise capacity in endurance athletes - G. Bernardino; M. Sanz de la Garza; B. Domenech-Ximenos; S. Prat-Gonzàlez; R. J. Perea; I. Blanco; F. Burgos; A. Sepulveda-Martinez; M. Rodriguez-Lopez; F. Crispi; C. Butakoff; M. A. González Ballester; et al. (European Journal of Applied Physiology, 2020)

A Metabolic Intravascular Platform to Study FDG Uptake in Vascular Injury - F. Franchi; M. Olthoff; J. Krier; C. Noble; M. Al-Hijji; V. Ramaswamy; T. Witt; M. Burke; M. Benscoter; A. Lerman; G. S. Sandhu; M. Rodriguez-Porcel (Cardiovascular Engineering and Technology, 2020)

Sub-Arctic Field Degradation of Metsulfuron-Methyl in Two Alaskan Soils and Microbial Community Composition Effects - Patrick L. Tomco; Steven S. Seefeldt; Katinna Rodriguez-Baisi; Jasmine J. Hatton; Khrystyne N. Duddleston (Water, Air, & Soil Pollution, 2020)

Sexual recombination within the “Kranich” race of the yellow rust fungus Puccinia striiformis f.sp. tritici on Berberis vulgaris - J. Rodriguez-Algaba; M. S. Hovmøller; A. F. Justesen (European Journal of Plant Pathology, 2020)

Adenovirus-Mediated Transduction of Insulin-Like Growth Factor 1 Protects Hippocampal Neurons from the Toxicity of Aβ Oligomers and Prevents Memory Loss in an Alzheimer Mouse Model - Maria Clara Selles; Juliana T. S. Fortuna; Maria F. Zappa-Villar; Yasmin P. R. de Faria; Amanda S. Souza; Claudia K. Suemoto; Renata E. P. Leite; Roberta D. Rodriguez; Lea T. Grinberg; Paula C. Reggiani; Sergio T. Ferreira (Molecular Neurobiology, 2020)

Evaluating the performance of freshwater macroalgae in the bioremediation of nutrient-enriched water in temperate environments - J. M. Valero-Rodriguez; S. E. Swearer; T. Dempster; R. de Nys; A. J. Cole (Journal of Applied Phycology, 2020)

SPEXOR passive spinal exoskeleton decreases metabolic cost during symmetric repetitive lifting - S. J. Baltrusch; J. H. van Dieën; A. S. Koopman; M. B. Näf; C. Rodriguez-Guerrero; J. Babič; H. Houdijk (European Journal of Applied Physiology, 2020)

Target of rapamycin signaling is tightly and differently regulated in the plant response under distinct abiotic stresses - Cintia M. Pereyra; Néstor R. Aznar; Marianela S. Rodriguez; Graciela L. Salerno; Giselle M. A. Martínez-Noël (Planta, 2020)

The interaction between temperature and dose on the efficacy and biochemical response of Atlantic salmon to hydrogen peroxide treatment for amoebic gill disease - James W. Wynne; Chris Stratford; Joel Slinger; Francisca Samsing; Megan Rigby; Russell McCulloch; Petra Quezada‐Rodriguez; Richard S. Taylor (Journal of Fish Diseases, 2020)
Hydrogen peroxide (H 2 O 2 ) is a commonly used treatment for a range of parasitic diseases of marine finfish, including amoebic gill disease (AGD). While this treatment is partially effective at reducing parasite load, H 2 O 2 can have detrimental effects on the host under certain conditions. Treatment temperature and dose concentration are two factors that are known to influence the toxicity of H 2 O 2 ; however, their impact on the outcome of AGD treatment remains unclear. Here, we investigated the effects of treatment temperature (8, 12 or 16°C) and dose concentration (750, 1,000, 1,250 mg/L) on the efficacy of H 2 O 2 to treat AGD. We demonstrated that a 20‐min bath treatment of H 2 O 2 at all doses reduced both parasite load and gross gill score significantly. Parasite load and gross gill score were lowest in the 1,000 mg/L treatment performed at 12°C. At the high dose and temperature combinations, H 2 O 2 caused moderate gill damage and a significant increase in the plasma concentration of electrolytes (sodium, chloride and potassium). Taken together, our study demonstrates that higher H 2 O 2 treatment temperatures can adversely affect the host and do not improve the effectiveness of the treatment.

Opioid-Induced Hyperalgesia Is Associated with Dysregulation of Circadian Rhythm and Adaptive Immune Pathways in the Mouse Trigeminal Ganglia and Nucleus Accumbens - Pan Zhang; Laura S. Moye; Bruce R. Southey; Isaac Dripps; Jonathan V. Sweedler; Amynah Pradhan; Sandra L. Rodriguez-Zas (Molecular Neurobiology, 2019)

Improving Research Literacy in Diverse Minority Populations with a Novel Communication Tool - Melissa A. Simon; Rodney Haring; Elisa M. Rodriguez; Evelyn González; Judith S. Kaur; Marcie Kirschner; Laura Tom; Catherine A. O’Brian; Mira L. Katz (Journal of Cancer Education, 2019)

Molecular and biochemical basis for the loss of bioluminescence in the dinoflagellate Noctiluca scintillans along the west coast of the U.S.A. - Martha Valiadi; Tristan de Rond; Ana Amorim; John R. Gittins; Chrysoula Gubili; Bradley S. Moore; Maria Debora Iglesias‐Rodriguez; Michael I. Latz (Limnology and Oceanography, 2019)
The globally distributed heterotrophic dinoflagellate Noctiluca scintillans (Macartney) Kofoid & Swezy is well known for its dense blooms and prominent displays of bioluminescence. Intriguingly, along the west coast of the U.S.A., its blooms are not bioluminescent. We investigated the basis for this regional loss of bioluminescence using molecular, cellular, and biochemical analyses of isolates from different geographic regions. Several prominent differences were identified in the nonbioluminescent strains: (1) the fused luciferase and luciferin binding protein gene ( lcf/lbp ) was present but its transcripts were undetectable; (2) lcf/lbp contained multiple potentially deleterious mutations; (3) the substrate luciferin was absent, based on the lack of luciferin blue autofluorescence and the absence of luciferin‐derived metabolites; (4) although the cells possessed scintillons, the organelles that contain the luminescent chemistry, electron microscopy revealed additional scintillon‐like organelles with an atypical internal structure; and (5) cells isolated from the California coast were 43% smaller than bioluminescent cells from the Gulf of Mexico. Phylogenetic analyses based on large subunit rDNA did not show divergence of the nonbioluminescent population in relation to bioluminescent N. scintillans from the Pacific Ocean and Arabian Sea. This study demonstrates that gene silencing and the lack of the luciferin substrate have resulted in the loss of an important dinoflagellate functional trait over large spatial scales in the ocean. As the bioluminescence system of dinoflagellates is well characterized, nonbioluminescent N. scintillans provide an ideal model to explore the evolutionary and ecological mechanisms that lead to intraspecific functional divergence in natural dinoflagellate populations.

Australia-Asian monsoon in two versions of the UK Met Office Unified Model and their impacts on tropical–extratropical teleconnections - L. Jin; H. Zhang; A. Moise; G. Martin; S. Milton; J. Rodriguez (Climate Dynamics, 2019)

Defining the indigenous ranges of species to account for geographic and taxonomic variation in the history of human impacts: reply to Sanderson 2019 - P. J. Stephenson; Molly K. Grace; H. Resit Akçakaya; Ana S. L. Rodrigues; Barney Long; David P. Mallon; Erik Meijaard; Jon Paul Rodriguez; Richard P. Young; Thomas M. Brooks; Craig Hilton‐Taylor (Conservation Biology, 2019)

Reorganization of the nuclear compartments involved in transcription and RNA processing in myonuclei of type I spinal muscular atrophy - María S. Castillo-Iglesias; María T. Berciano; J. Oriol Narcis; J. Fernando Val-Bernal; José C. Rodriguez-Rey; Olga Tapia; Miguel Lafarga (Histochemistry and Cell Biology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Remotely Sensed Winds and Wind Stresses for Marine Forecasting and Ocean Modeling - Mark A. Bourassa; Thomas Meissner; Ivana Cerovecki; Paul S. Chang; Xiaolong Dong; Giovanna De Chiara; Craig Donlon; Dmitry S. Dukhovskoy; Jocelyn Elya; Alexander Fore; Melanie R. Fewings; Ralph C. Foster; et al. (Frontiers in Marine Science, 2019)

The exocrine pancreas is an extracardiac source of atrial natriuretic peptide - Ana C. Najenson; Mariana Bianchi; Ana P. Courreges; Myrian R. Rodriguez; Víctor H. Casco; Marcelo S. Vatta; Liliana G. Bianciotti (Pflügers Archiv - European Journal of Physiology, 2019)

Bioethanol Production From Sugarcane Bagasse Hemicellulose Hydrolysate by Immobilized S. shehatae in a Fluidized Bed Fermenter Under Magnetic Field - Kelly J. Dussán; Oselys Rodriguez Justo; Victor Haber Perez; Geraldo F. David; Euripedes Garcia Silveira Junior; Silvio S. da Silva (BioEnergy Research, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Doubting dung: eDNA reveals high rates of misidentification in diverse European ungulate communities - Robert Spitzer; Marcin Churski; Annika Felton; Marco Heurich; Dries P. J. Kuijper; Marietjie Landman; Esther Rodriguez; Navinder J. Singh; Pierre Taberlet; Suzanne T. S. van Beeck Calkoen; Fredrik Widemo; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2019)

Genotypic Variation and Phenotypic Plasticity in Gene Expression and Emissions of Herbivore-Induced Volatiles, and their Potential Tritrophic Implications, in Cranberries - Elvira S. De Lange; Jordano Salamanca; James Polashock; Cesar Rodriguez-Saona (Journal of Chemical Ecology, 2019)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Invasive pulmonary aspergillosis is associated with adverse clinical outcomes in critically ill patients receiving veno-venous extracorporeal membrane oxygenation - I. Rodriguez-Goncer; S. Thomas; P. Foden; M. D. Richardson; A. Ashworth; J. Barker; C. G. Geraghty; E. G. Muldoon; T. W. Felton (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Metal contaminations impact archaeal community composition, abundance and function in remote alpine lakes - Sergi Compte‐Port; Carles M. Borrego; Hélène Moussard; Mathilde Jeanbille; Claudia Ximena Restrepo‐Ortiz; Alberto de Diego; Azibar Rodriguez‐Iruretagoiena; Ainara Gredilla; Silvia Fdez‐Ortiz de Vallejuelo; Pierre E. Galand; Dimitri Kalenitchenko; Jean‐Luc Rols; et al. (Environmental Microbiology, 2018)
Summary Using the 16S rRNA and mcrA genes, we investigated the composition, abundance and activity of sediment archaeal communities within 18 high‐mountain lakes under contrasted metal levels from different origins (bedrock erosion, past‐mining activities and atmospheric depositions). Bathyarchaeota, Euryarchaeota and Woesearchaeota were the major phyla found at the meta‐community scale, representing 48%, 18.3% and 15.2% of the archaeal community respectively. Metals were equally important as physicochemical variables in explaining the assemblage of archaeal communities and their abundance. Methanogenesis appeared as a process of central importance in the carbon cycle within sediments of alpine lakes as indicated by the absolute abundance of methanogen 16S rRNA and mcrA gene transcripts (10 5 to 10 9 copies g −1 ). We showed that methanogen abundance and activity were significantly reduced with increasing concentrations of Pb and Cd, two indicators of airborne metal contaminations. Considering the ecological importance of methanogenesis in sediment habitats, these metal contaminations may have system wide implications even in remote area such as alpine lakes. Overall, this work was pioneer in integrating the effect of long‐range atmospheric depositions on archaeal communities and indicated that metal contamination might significantly compromise the contribution of Archaea to the carbon cycling of the mountain lake sediments.

Role of Plant Volatiles in Host Plant Recognition by Listronotus maculicollis (Coleoptera: Curculionidae) - Olga S. Kostromytska; Cesar Rodriguez-Saona; Hans T. Alborn; Albrecht M. Koppenhöfer (Journal of Chemical Ecology, 2018)

A Novel Application of Indocyanine Green Immunofluorescence in Emergent Colorectal Surgery - Deborah S. Keller; Richard Boulton; Manuel Rodriguez-Justo; Richard Cohen; Manish Chand (Journal of Fluorescence, 2018)

Impact of activated sludge acclimation on the biodegradation of toluene absorbed in a hydrophobic ionic liquid - A. S. Rodriguez Castillo; S. Guihéneuf; P.-F. Biard; L. Paquin; A. Amrane; A. Couvert (International Journal of Environmental Science and Technology, 2018)

RNA interference-based therapy and its delivery systems - Xiuhui Chen; Lingegowda S. Mangala; Cristian Rodriguez-Aguayo; Xianchao Kong; Gabriel Lopez-Berestein; Anil K. Sood (Cancer and Metastasis Reviews, 2018)

Trace metals in the soils of Water Conservation Area of Florida Everglades: Considerations for ecosystem restoration - Salwinder S. Dhaliwal; Gurpal S. Toor; Ignacio A. Rodriguez-Jorquera; Todd Z. Osborne; Susan Newman (Journal of Soils and Sediments, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Evaluation of heteroatom-rich derivatives as antitubercular agents with InhA inhibition properties - Bachar Rébat Moulkrere; Beatrice S. Orena; Giorgia Mori; Nathalie Saffon-Merceron; Frédéric Rodriguez; Christian Lherbet; Nadji Belkheiri; Mohamed Amari; Pascal Hoffmann; Mokhtar Fodili (Medicinal Chemistry Research, 2018)

Anisotropic larval connectivity and metapopulation structure driven by directional oceanic currents in a marine fish targeted by small-scale fisheries - Adrian Munguia-Vega; S. Guido Marinone; David A. Paz-Garcia; Alfredo Giron-Nava; Tomas Plomozo-Lugo; Ollin Gonzalez-Cuellar; Amy Hudson Weaver; Francisco J. García-Rodriguez; Hector Reyes-Bonilla (Marine Biology, 2018)

Photosynthetic performance and pigment composition of Macrocystis pyrifera (Laminariales, Phaeophyceae) along a gradient of depth and seasonality in the ecoregion of Magellan, Chile - J. Marambio; J. P. Rodriguez; F. Mendez; P. Ocaranza; S. Rosenfeld; J. Ojeda; R. Rautenberger; K. Bischof; J. Terrados; A. Mansilla (Journal of Applied Phycology, 2017)

Nutritional properties of dishes prepared with sub-Antarctic macroalgae—an opportunity for healthy eating - Ma. S. Astorga-España; A. Mansilla; J. Ojeda; J. Marambio; S. Rosenfeld; F. Mendez; J. P. Rodriguez; P. Ocaranza (Journal of Applied Phycology, 2017)

Environment and life cycles influence distribution patterns of hydromedusae in austral South America - Carolina S. Rodriguez; Antonio C. Marques; Hermes W. Mianzan; Valquiria B. Tronolone; Alvaro E. Migotto; Gabriel N. Genzano (Marine Biology Research, 2017)

Effects of diurnal temperature range and drought on wheat yield in Spain - S. Hernandez-Barrera; C. Rodriguez-Puebla; A. J. Challinor (Theoretical and Applied Climatology, 2017)

Adaptation of Shigella flexneri to starvation: morphology, outer membrane proteins and lipopolysaccharide changes - K. Chourabi; F. Torrella; S. Kloula; J. A. Rodriguez; I. Trabelsi; S. Campoy; A. Landoulsi; A. Chatti (Arabian Journal of Geosciences, 2017)

A comparison of psychotic symptoms in subjects with methamphetamine versus cocaine dependence - Peter D Alexander; Kristina M Gicas; Taylor S Willi; Clara N Kim; Veronika Boyeva; Ric M Procyshyn; Geoff N. Smith; Allen E Thornton; William J Panenka; Andrea A. Jones; Fidel Vila-Rodriguez; Donna J. Lang; et al. (Psychopharmacology, 2017)

Seasonal variations of the photosynthetic activity and pigment concentrations in different reproductive phases of Gigartina skottsbergii (Rhodophyta, Gigartinales) in the Magellan region, sub-Antarctic Chile - J. Marambio; F. Mendez; P. Ocaranza; J. P. Rodriguez; S. Rosenfeld; J. Ojeda; S. Murcia; J. Terrados; K. Bischof; A . Mansilla (Journal of Applied Phycology, 2017)

Epidemiology and reporting of candidaemia in Belgium: a multi-centre study - C. Trouvé; S. Blot; M.-P. Hayette; S. Jonckheere; S. Patteet; H. Rodriguez-Villalobos; F. Symoens; E. Van Wijngaerden; K. Lagrou (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

The effect of future climate change on the conservation of Chloraea disoides Lindl. (Orchidaceae) in Chile - C. Atala; L. Muñoz-Tapia; G. Pereira; C. Romero; R. Vargas; I. S. Acuña-Rodriguez; M. A. Molina-Montenegro; E. Brito (Brazilian Journal of Botany, 2017)

Lizards fail to plastically adjust nesting behavior or thermal tolerance as needed to buffer populations from climate warming - Rory S. Telemeco; Brooke Fletcher; Ofir Levy; Angela Riley; Yesenia Rodriguez‐Sanchez; Colton Smith; Collin Teague; Amanda Waters; Michael J. Angilletta; Lauren B. Buckley (Global Change Biology, 2017)
Although observations suggest the potential for phenotypic plasticity to allow adaptive responses to climate change, few experiments have assessed that potential. Modeling suggests that Sceloporus tristichus lizards will need increased nest depth, shade cover, or embryonic thermal tolerance to avoid reproductive failure resulting from climate change. To test for such plasticity, we experimentally examined how maternal temperatures affect nesting behavior and embryonic thermal sensitivity. The temperature regime that females experienced while gravid did not affect nesting behavior, but warmer temperatures at the time of nesting reduced nest depth. Additionally, embryos from heat‐stressed mothers displayed increased sensitivity to high‐temperature exposure. Simulations suggest that critically low temperatures, rather than high temperatures, historically limit development of our study population. Thus, the plasticity needed to buffer this population has not been under selection. Plasticity will likely fail to compensate for ongoing climate change when such change results in novel stressors.

South American PSP toxin-producing Cylindrospermopsis raciborskii (Cyanobacteria) decreases clearance rates of cladocerans more than copepods - Amelia Fabre; Gissell Lacerot; Rafael Rodriguez de Paiva; M. Carolina S. Soares; Valéria Freitas de Magalhães; Sylvia Bonilla (Hydrobiologia, 2017)

Sources of trace metals in PM10 from a petrochemical industrial complex in Northern Mexico - P. F. Rodriguez-Espinosa; R. M. Flores-Rangel; V. Mugica-Alvarez; S. S. Morales-Garcia (Air Quality, Atmosphere & Health, 2017)

Experimental and DFT characterization, antioxidant and anticancer activities of a Cu(II)–irbesartan complex: structure–antihypertensive activity relationships in Cu(II)–sartan complexes - María S. Islas; Alicia Luengo; Carlos A. Franca; Mercedes Griera Merino; Laura Calleros; Manuel Rodriguez-Puyol; Luis Lezama; Evelina G. Ferrer; Patricia A. M. Williams (JBIC Journal of Biological Inorganic Chemistry, 2016)

Free-living culturable bacteria and protozoa from the rhizoplanes of three floating aquatic plant species - E. Quisehuatl-Tepexicuapan; R. Ferrera-Cerrato; H. V. Silva-Rojas; S. Rodriguez-Zaragoza; A. Alarcón; J. J. Almaraz-Suárez (Plant Biosystems, 2016)

Genotype Number and Allelic Diversity Overview in the National Collection of Chilean Potatoes - M. Muñoz; C. Folch; F. Rodriguez; J. Kalazich; S. Orena; J. Santos; R. Vargas; A. Fahrenkrog; A. Puga (Potato Research, 2016)

Neisseria gonorrhoeae antimicrobial susceptibility in Barcelona: penA, ponA, mtrR, and porB mutations and NG-MAST sequence types associated with decreased susceptibility to cephalosporins - J. Serra-Pladevall; M. J. Barberá; S. Rodriguez; R. Bartolomé-Comas; G. Roig; R. Juvé; A. Andreu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Effectiveness of sequential intravenous-to-oral antibiotic switch therapy in hospitalized patients with gram-positive infection: the SEQUENCE cohort study - D. Rodriguez-Pardo; C. Pigrau; D. Campany; V. Diaz-Brito; L. Morata; I. C. de Diego; L. Sorlí; S. Iftimie; R. Pérez-Vidal; G. García-Pardo; T. Larrainzar-Coghen; B. Almirante (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Amphibian‐killing chytrid in B razil comprises both locally endemic and globally expanding populations - T. S. Jenkinson; C. M. Betancourt Román; C. Lambertini; A. Valencia‐Aguilar; D. Rodriguez; C. H. L. Nunes‐de‐Almeida; J. Ruggeri; A. M. Belasen; D. da Silva Leite; K. R. Zamudio; J. E. Longcore; L. F. Toledo; et al. (Molecular Ecology, 2016)
Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis ( Bd ), is the emerging infectious disease implicated in recent population declines and extinctions of amphibian species worldwide. Bd strains from regions of disease‐associated amphibian decline to date have all belonged to a single, hypervirulent clonal genotype ( Bd ‐ GPL ). However, earlier studies in the Atlantic Forest of southeastern Brazil detected a novel, putatively enzootic lineage ( Bd ‐Brazil), and indicated hybridization between Bd ‐ GPL and Bd ‐Brazil. Here, we characterize the spatial distribution and population history of these sympatric lineages in the Brazilian Atlantic Forest. To investigate the genetic structure of Bd in this region, we collected and genotyped Bd strains along a 2400‐km transect of the Atlantic Forest. Bd ‐Brazil genotypes were restricted to a narrow geographic range in the southern Atlantic Forest, while Bd ‐ GPL strains were widespread and largely geographically unstructured. Bd population genetics in this region support the hypothesis that the recently discovered Brazilian lineage is enzootic in the Atlantic Forest of Brazil and that Bd ‐ GPL is a more recently expanded invasive. We collected additional hybrid isolates that demonstrate the recurrence of hybridization between panzootic and enzootic lineages, thereby confirming the existence of a hybrid zone in the Serra da Graciosa mountain range of Paraná State. Our field observations suggest that Bd ‐ GPL may be more infective towards native Brazilian amphibians, and potentially more effective at dispersing across a fragmented landscape. We also provide further evidence of pathogen translocations mediated by the Brazilian ranaculture industry with implications for regulations and policies on global amphibian trade.

Effect of Microwave-Assisted Pretreatment Conditions on Hemicellulose Conversion and Enzymatic Hydrolysis of Norway Spruce - S. Kuittinen; Y. Puentes Rodriguez; M. Yang; M. Keinänen; O. Pastinen; M. Siika-aho; O. Turunen; A. Pappinen (BioEnergy Research, 2016)

Overview of Integrative Assessment of Marine Systems: The Ecosystem Approach in Practice - Angel Borja; Michael Elliott; Jesper H. Andersen; Torsten Berg; Jacob Carstensen; Benjamin S. Halpern; Anna-Stiina Heiskanen; Samuli Korpinen; Julia S. Stewart Lowndes; Georg Martin; Naiara Rodriguez-Ezpeleta (Frontiers in Marine Science, 2016)

Assessing stakeholder impacts and adaptation to low water-levels: the Trent-Severn waterway - J. M. A. Coleman; F. S. Sosa-Rodriguez; L. D. Mortsch; P. J. Deadman (Climatic Change, 2016)

Metal enrichment of soils following the April 2012–2013 eruptive activity of the Popocatépetl volcano, Puebla, Mexico - P. F. Rodriguez-Espinosa; M. P. Jonathan; S. S. Morales-García; Lorena Elizabeth Campos Villegas; E. Martínez-Tavera; N. P. Muñoz-Sevilla; Miguel Alvarado Cardona (Environmental Monitoring and Assessment, 2015)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Cellular metabolism of unnatural sialic acid precursors - Nam D. Pham; Charles S. Fermaintt; Andrea C. Rodriguez; Janet E. McCombs; Nicole Nischan; Jennifer J. Kohler (Glycoconjugate Journal, 2015)

Discriminative stimulus and hypothermic effects of some derivatives of the nAChR agonist epibatidine in mice - Jesse S. Rodriguez; Colin S. Cunningham; Fernando B. Moura; Pauline Ondachi; F. Ivy Carroll; Lance R. McMahon (Psychopharmacology, 2014)

Regional status assessment of stony corals in the US Virgin Islands - William S. Fisher; Leska S. Fore; Leah M. Oliver; Charles Lobue; Robert Quarles; Jed Campbell; Peggy Harris; Becky Hemmer; Sherry Vickery; Mel Parsons; Aaron Hutchins; Kent Bernier; et al. (Environmental Monitoring and Assessment, 2014)

Establishment and characterization of a new cell line ( SSP ‐9) derived from Atlantic salmon Salmo salar that expresses type I if n - S. Rodriguez Saint‐Jean; C. González; M. Monrás; A. Romero; N. Ballesteros; R. Enríquez; S. Perez‐Prieto (Journal of Fish Biology, 2014)
In the present work, the establishment and biological characterization of a new cell line, SSP ‐9, derived from the pronephros of the Atlantic salmon Salmo salar , are reported. These cells grew well in Leibovitz's ( L15 ) medium supplemented with 10% foetal calf serum at temperatures from 15 to 25 ° C , and they have been sub‐cultured over 100 passages to produce a continuous cell line with an epithelial‐like morphology. The SSP ‐9 cells attached and spread efficiently at different plating densities, retaining 80% of cell viability after storage in liquid nitrogen. When karyotyped, the cells had 40–52 chromosomes, with a modal number of 48. Viral susceptibility tests showed that SSP ‐9 cells were susceptible to infectious pancreatic necrosis virus and infectious haematopoietic necrosis virus, producing infectious virus and regular cytopathic effects. Moreover, these cells could be stimulated by poly I:C, showing significant up‐regulation in the expression of the genes that regulate immune responses, such as ifn and mx‐1 . SSP ‐9 cells constitutively express genes characteristic of macrophages, such as major histocompatibility complex ( mhc‐ II ) and interleukin 12b ( il‐12b ), and flow cytometry assays confirmed that SSP ‐9 cells can be permanently transfected with plasmids expressing a reporter gene. Accordingly, this new cell line is apparently suitable for transgenic manipulation, and to study host cell–virus interactions and immune processes.

Engaging diverse populations about biospecimen donation for cancer research - Julie H. T. Dang; Elisa M. Rodriguez; John S. Luque; Deborah O. Erwin; Cathy D. Meade; Moon S. Chen (Journal of Community Genetics, 2014)

From federal to city mitigation and adaptation: climate change policy in Mexico City - Fabiola S. Sosa-Rodriguez (Mitigation and Adaptation Strategies for Global Change, 2014)

Identifying the pollen of an extinct spruce species in the Late Quaternary sediments of the Tunica Hills region, south‐eastern United States - L. MANDER; J. RODRIGUEZ; P. G. MUELLER; S. T. JACKSON; S. W. PUNYASENA (Journal of Quaternary Science, 2014)
Late Quaternary fluvial deposits in the Tunica Hills region of Louisiana and Mississippi are rich in spruce macrofossils of the extinct species Picea critchfieldii , the one recognized plant extinction of the Late Quaternary. However, the morphology of P. critchfieldii pollen is unknown, presenting a barrier to the interpretation of pollen spectra from the last glacial of North America. To address this issue, we undertook a morphometric study of Picea pollen from Tunica Hills. Morphometric data, together with qualitative observations of pollen morphology using Apotome fluorescence microscopy, indicate that Picea pollen from Tunica Hills is morphologically distinct from the pollen of P. glauca , P. mariana and P. rubens . Measurements of grain length, corpus width and corpus height indicate that Picea pollen from Tunica Hills is larger than the pollen of P. mariana and P. rubens , and is slightly larger than P. glauca pollen. We argue that the morphologically distinctive Tunica Hills Picea pollen was probably produced by the extinct spruce species P. critchfieldii . These morphological differences could be used to identify P. critchfieldii in existing and newly collected pollen records, which would refine its paleoecologic and biogeographic history and clarify the nature and timing of its extinction in the Late Quaternary.

Strategies to evaluate biodegradability: application to chlorinated herbicides - S. Sanchis; A. M. Polo; M. Tobajas; J. J. Rodriguez; A. F. Mohedano (Environmental Science and Pollution Research, 2014)

Quetiapine extended-release (Seroquel-XR) versus amitriptyline monotherapy for treating patients with fibromyalgia: a 16-week, randomized, flexible-dose, open-label trial - Elena P. Calandre; Fernando Rico-Villademoros; Jaime Galán; Rocio Molina-Barea; Juan S. Vilchez; Carmen M. Rodriguez-Lopez; Javier Hidalgo-Tallon; Piedad Morillas-Arques (Psychopharmacology, 2014)

Growth responses to temperature, salinity and nutrient variations, and biomass variation and phenology of Ahnfeltia plicata (Rhodophyta, Ahnfeltiales): a commercially interesting agarophyte from the Magellanic Region, Chile - Andres Mansilla; Juan Pablo Rodriguez; Jonatas M. C. Souza; Sebastián Rosenfeld; Jaime Ojeda; Nair S. Yokoya (Journal of Applied Phycology, 2014)

FMLP-, thapsigargin-, and H2O2-evoked changes in intracellular free calcium concentration in lymphocytes and neutrophils of type 2 diabetic patients - Shanti S. Kappala; Javier Espino; Jose A. Pariente; Ana B. Rodriguez; Satyan Rajbhandari; Arati Iyengar; Keshore R. Bidasee; Jaipaul Singh (Molecular and Cellular Biochemistry, 2014)

Brassica Plant Responses to Mild Herbivore Stress Elicited by Two Specialist Insects from Different Feeding Guilds - P. Sotelo; E. Pérez; A. Najar-Rodriguez; A. Walter; S. Dorn (Journal of Chemical Ecology, 2014)

Fruit Wastes Fermentation for Phenolic Antioxidants Production and Their Application in Manufacture of Edible Coatings and Films - G. C. G. Martinez-Avila; A. F. Aguilera; S. Saucedo; R. Rojas; R. Rodriguez; C. N. Aguilar (Critical Reviews in Food Science and Nutrition, 2014)

Bivalve distribution in hydrographic regions in South America: historical overview and conservation - Daniel Pereira; Maria Cristina Dreher Mansur; Leandro D. S. Duarte; Arthur Schramm de Oliveira; Daniel Mansur Pimpão; Cláudia Tasso Callil; Cristián Ituarte; Esperanza Parada; Santiago Peredo; Gustavo Darrigran; Fabrizio Scarabino; Cristhian Clavijo; et al. (Hydrobiologia, 2013)

Fungal endophytes of invasive Phagramites australis populations vary in species composition and fungicide susceptibility - Monika S. Fischer; Rusty J. Rodriguez (Symbiosis, 2013)

Erratum to: Social signals increase monoamine levels in the tegmentum of juvenile Mexican spadefoot toads (Spea multiplicata) - Verónica G. Rodriguez Moncalvo; Sabrina S. Burmeister; Karin S. Pfennig (Journal of Comparative Physiology A, 2013)

Social signals increase monoamine levels in the tegmentum of juvenile Mexican spadefoot toads (Spea multiplicata) - Verónica G. Rodriguez Moncalvo; Sabrina S. Burmeister; Karin S. Pfennig (Journal of Comparative Physiology A, 2013)

Technical and Economic Analysis of Aeroponics and other Systems for Potato Mini-Tuber Production in Latin America - Julian R. Mateus-Rodriguez; Stef de Haan; Jorge L. Andrade-Piedra; Luis Maldonado; Guy Hareau; Ian Barker; Carlos Chuquillanqui; Victor Otazú; Rebeca Frisancho; Carolina Bastos; Arione S. Pereira; Carlos A. Medeiros; et al. (American Journal of Potato Research, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

Acclimation to Elevated CO2 Increases Constitutive Glucosinolate Levels of Brassica Plants and Affects the Performance of Specialized Herbivores from Contrasting Feeding Guilds - J. Klaiber; S. Dorn; A. J. Najar-Rodriguez (Journal of Chemical Ecology, 2013)

Investigations into the differential reactivity of endogenous and exogenous mercury species in coastal sediments - S. Bouchet; P. Rodriguez-Gonzalez; R. Bridou; M. Monperrus; E. Tessier; P. Anschutz; R. Guyoneaud; D. Amouroux (Environmental Science and Pollution Research, 2013)

Spatial impact of projected changes in rainfall and temperature on wheat yields in Australia - A. Potgieter; H. Meinke; A. Doherty; V. O. Sadras; G. Hammer; S. Crimp; D. Rodriguez (Climatic Change, 2013)

Season-Long Volatile Emissions from Peach and Pear Trees In Situ, Overlapping Profiles, and Olfactory Attraction of an Oligophagous Fruit Moth in the Laboratory - A. Najar-Rodriguez; B. Orschel; S. Dorn (Journal of Chemical Ecology, 2013)

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

The droughts of 1997 and 2005 in Amazonia: floodplain hydrology and its potential ecological and human impacts - Javier Tomasella; Patrícia F. Pinho; Laura S. Borma; José A. Marengo; Carlos A. Nobre; Olga R. F. O. Bittencourt; Maria C. R. Prado; Daniel A. Rodriguez; Luz A. Cuartas (Climatic Change, 2013)

Description of a new hydromedusa from the southwestern A tlantic O cean, B ougainvillia pagesi sp. nov. ( C nidaria, H ydrozoa, A nthoathecata) - Miodeli Nogueira; Carolina S. Rodriguez; Hermes Mianzan; Maria A. Haddad; Gabriel Genzano (Marine Ecology, 2013)
A new hydromedusa species of the genus Bougainvillia (Anthoathecata; Bougainvillidae) is described. Bougainvillia pagesi sp. nov. was collected in shallow coastal waters from southern Brazil (~25–26°S) and northern Argentina (~36–38°S). It differs from other species of the genus mainly by two characters: (i) relatively large size (up to ~20 mm wide and high) and (ii) voluminous folded hanging gonads at perradial walls of the manubrium and extending to the proximal region of the radial canals. Its cnidoma is similar to the other species of the genus, with desmonemes (undischarged capsules: 7.08–10.01 × 2.5–5.59 μm) at marginal tentacles and microbasic euryteles (undischarged capsules: 7.66–11.44 × 2.64–4.43 μm) and smaller (undischarged capsules

Characterization of CCDC28B reveals its role in ciliogenesis and provides insight to understand its modifier effect on Bardet–Biedl syndrome - Magdalena Cardenas-Rodriguez; Daniel P. S. Osborn; Florencia Irigoín; Martín Graña; Héctor Romero; Philip L. Beales; Jose L. Badano (Human Genetics, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Zygomycosis Caused by Rhizopus microsporus and Rhizopus oryzae in Madhya Pradesh (M.P.) Central India: A Report of Two Cases - Shesh R. Nawange; S. M. Singh; J. Naidu; S. Jain; T. Nagpal; D. S. Behrani; E. Mellado; J. L. Rodriguez Tudela (Mycopathologia, 2012)

Impact of Earth radiation pressure on GPS position estimates - C. J. Rodriguez-Solano; U. Hugentobler; P. Steigenberger; S. Lutz (Journal of Geodesy, 2012)

Molecular characterization of Staphylococcus aureus from outpatients in the Caribbean reveals the presence of pandemic clones - A.-C. Uhlemann; C. Dumortier; C. Hafer; B. S. Taylor; J. Sánchez E.; C. Rodriguez-Taveras; P. Leon; R. Rojas; C. Olive; F. D. Lowy (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Opacification of Shape Memory Polymer Foam Designed for Treatment of Intracranial Aneurysms - Jennifer N. Rodriguez; Ya-Jen Yu; Matthew W. Miller; Thomas S. Wilson; Jonathan Hartman; Fred J. Clubb; Brandon Gentry; Duncan J. Maitland (Annals of Biomedical Engineering, 2012)

The Cassava Genome: Current Progress, Future Directions - Simon Prochnik; Pradeep Reddy Marri; Brian Desany; Pablo D. Rabinowicz; Chinnappa Kodira; Mohammed Mohiuddin; Fausto Rodriguez; Claude Fauquet; Joseph Tohme; Timothy Harkins; Daniel S. Rokhsar; Steve Rounsley (Tropical Plant Biology, 2012)

Jatropha adoption: a statistical observational study of factors influencing Malian farmers’ decision to grow Jatropha - M. Basinger; J. Chen; F. Jeffrey-Coker; F. S. Rodriguez-Sanchez; T. Singer; V. Modi (Agroforestry Systems, 2012)

On the effects of the ionospheric disturbances on precise point positioning at equatorial latitudes - B. Moreno; S. Radicella; M. C. de Lacy; M. Herraiz; G. Rodriguez-Caderot (GPS Solutions, 2011)

Qualitative Evaluation of a New Tobacco Cessation Training Curriculum for Patient Navigators - Jamie S. Ostroff; Elyse Shuk; Paul Krebs; Wei-Hsin Lu; Jack Burkhalter; Jeralyn Cortez-Weir; Rian Rodriguez; Vanessa N. Burnside; Erica I. Lubetkin (Journal of Cancer Education, 2011)

Antifungal activity of sakurasosaponin from the root extract of Jacquinia flammea - K. García-Sosa; A. Sánchez-Medina; Sandra L. Álvarez; S. Zacchino; N.C. Veitch; P. Simá-Polanco; L.M. Peña-Rodriguez (Natural Product Research, 2011)

Effect of human-mediated migration and hybridization on the recovery of the American crocodile in Florida (USA) - David Rodriguez; Michael R. J. Forstner; Paul E. Moler; Joseph A. Wasilewski; Michael S. Cherkiss; Llewellyn D. Densmore III (Conservation Genetics, 2011)

Effects of density, climate, and supplementary forage on body mass and pregnancy rates of female red deer in Spain - P. Rodriguez-Hidalgo; C. Gortazar; F. S. Tortosa; C. Rodriguez-Vigal; Y. Fierro; J. Vicente (Oecologia, 2010)

Late Holocene climate and environment of the SE Pampa grasslands, Argentina, inferred from biological indicators in shallow, freshwater Lake Nahuel Rucá - Silvina Stutz; C. Marcela Borel; Sonia L. Fontana; Laura del Puerto; Hugo Inda; Felipe García-Rodriguez; Marcela S. Tonello (Journal of Paleolimnology, 2010)

Molecular, Biochemical, and Organismal Analyses of Tomato Plants Simultaneously Attacked by Herbivores from Two Feeding Guilds - Cesar R. Rodriguez-Saona; Richard O. Musser; Heiko Vogel; Sue M. Hum-Musser; Jennifer S. Thaler (Journal of Chemical Ecology, 2010)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Characterization of three sect. Caulopterae species (Baccharis-Asteraceae) inferred from morphoanatomy, polypeptide profiles and spectrophotometry data - M. V. Rodriguez; M. L. Martínez; A. A. Cortadi; A. Bandoni; D. A. Giuliano; S. J. Gattuso; M. A. Gattuso (Plant Systematics and Evolution, 2010)

Zooplankton response to shading effects of free-floating plants in shallow warm temperate lakes: a field mesocosm experiment - M. S. Fontanarrosa; G. Chaparro; P. de Tezanos Pinto; P. Rodriguez; I. O’Farrell (Hydrobiologia, 2010)

‘Alternate-goal bias’ in antisaccades and the influence of expectation - Mathias Abegg; Amadeo R. Rodriguez; Hyung Lee; Jason J. S. Barton (Experimental Brain Research, 2010)

Transcriptome analysis of resistant and susceptible genotypes of Glycine tomentella during Phakopsora pachyrhizi infection reveals novel rust resistance genes - Ruth Elena Soria-Guerra; Sergio Rosales-Mendoza; Sungyul Chang; James S. Haudenshield; Annamalai Padmanaban; Sandra Rodriguez-Zas; Glen L. Hartman; Said A. Ghabrial; Schuyler S. Korban (Theoretical and Applied Genetics, 2010)

Chromosomal banding in three species of the genus Rineloricaria (Siluriformes, Loricariidae, Loricariinae) - T. P. de A. Maia; Lucia Giuliano-Caetano; Mônica S. Rodriguez; Marceléia Rubert; Fabio Hiroshi Takagui; Ana Lúcia Dias (Ichthyological Research, 2010)

Why do humans make antisaccade errors? - Hyung Lee; Mathias Abegg; Amadeo Rodriguez; John Koehn; Jason J. S. Barton (Experimental Brain Research, 2010)

Long‐term transpiration change with rainfall decline in a Mediterranean Quercus ilex forest - J. M. LIMOUSIN; S. RAMBAL; J. M. OURCIVAL; A. ROCHETEAU; R. JOFFRE; R. RODRIGUEZ‐CORTINA (Global Change Biology, 2009)
In the Mediterranean basin, precipitation is expected to decline as a consequence of climate change. The response of a Quercus ilex forest in southern France to such a decline in water availability was studied using a 4‐year throughfall exclusion experiment. Seasonal courses of sap flow and leaf water potential were obtained from 2004 to 2007 and used to characterize tree water relations in a control and a dry treatment. The experiment reduced the average precipitation input to the soil by 29%, and resulted in a 23% reduction in annual transpiration. Soil water potential was significantly lower in the dry treatment only during summer drought, but transpiration was reduced all year round even during well‐watered periods. Despite a tight stomatal control over transpiration, whole‐tree hydraulic conductance was found to be lower in the trees growing in the driest conditions. This reduction in water transport capacity was observed jointly with a reduction in leaf transpiring area. Canopy leaf area decreased by 18% in the dry treatment as a consequence of the throughfall exclusion, which was found to validate the ecohydrological equilibrium theory.

Shallow lake trophic status linked to late Holocene climate and human impacts - Matthew N. Waters; Michael F. Piehler; Antonio B. Rodriguez; Joseph M. Smoak; Thomas S. Bianchi (Journal of Paleolimnology, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Osteomyelitis of the jaw: resistance to clindamycin in patients with prior antibiotics exposure - C. Pigrau; B. Almirante; D. Rodriguez; N. Larrosa; S. Bescos; G. Raspall; A. Pahissa (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Molecular characterization of a foot-and-mouth disease virus containing a 57-nucleotide insertion in the 3′untranslated region - M. E. Piccone; S. Pauszek; J. Pacheco; E. Rieder; E. Kramer; L. L. Rodriguez (Archives of Virology, 2009)

Overexpression of WUSCHEL in C. chinense causes ectopic morphogenesis - L. Y. Solís-Ramos; T. González-Estrada; S. Nahuath-Dzib; L. C. Zapata-Rodriguez; E. Castaño (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Sex Pheromone of the Scarab Beetle Phyllophaga (Phytalus) georgiana (Horn) - Paul S. Robbins; Satoshi Nojima; Sridhar Polavarapu; Albrecht M. Koppenhöfer; Cesar Rodriguez-Saona; Robert J. Holdcraft; Nancy H. Consolie; Daniel C. Peck; Wendell L. Roelofs (Journal of Chemical Ecology, 2009)

Scintillometer Intercomparison Study—Continued - J. Kleissl; C. J. Watts; J. C. Rodriguez; S. Naif; E. R. Vivoni (Boundary-Layer Meteorology, 2009)

Phytolacca americana from Contaminated and Noncontaminated Soils of South Korea: Effects of Elevated Temperature, CO2 and Simulated Acid Rain on Plant Growth Response - Yong Ok Kim; Rusty J. Rodriguez; Eun Ju Lee; Regina S. Redman (Journal of Chemical Ecology, 2008)

Role of Copper and Homocysteine in Pressure Overload Heart Failure - William M. Hughes; Walter E. Rodriguez; Dorothea Rosenberger; Jing Chen; Utpal Sen; Neetu Tyagi; Karni S. Moshal; Thomas Vacek; Y. James Kang; Suresh C. Tyagi (Cardiovascular Toxicology, 2008)

Genetic characterization and molecular epidemiology of foot-and-mouth disease viruses isolated from Afghanistan in 2003–2005 - Kate R. Schumann; Nick J. Knowles; Paul R. Davies; Rebecca J. Midgley; Jean-Francois Valarcher; Abdul Quader Raoufi; Thomas S. McKenna; William Hurtle; James P. Burans; Barbara M. Martin; Luis L. Rodriguez; Tammy R. Beckham (Virus Genes, 2008)

A marker-assisted backcross approach for developing submergence-tolerant rice cultivars - C. N. Neeraja; R. Maghirang-Rodriguez; A. Pamplona; S. Heuer; B. C. Y. Collard; E. M. Septiningsih; G. Vergara; D. Sanchez; K. Xu; A. M. Ismail; D. J. Mackill (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Nuclear DNA content of Vitis vinifera cultivars and ploidy level analyses of somatic embryo-derived plants obtained from anther culture - F. Leal; J. Loureiro; E. Rodriguez; M. S. Pais; C. Santos; O. Pinto-Carnide (Plant Cell Reports, 2006)

A Polymerase Chain Reaction Screening Method for Rapid Detection of Microsatellites in Bacterial Artificial Chromosomes - M. F. Rodriguez; S. A. Gahr; C. E. Rexroad; Y. Palti (Marine Biotechnology, 2006)

Successful treatment of septic shock due to pan-resistant Acinetobacter baumannii using combined antimicrobial therapy including tigecycline - F. S. Taccone; H. Rodriguez-Villalobos; D. De Backer; V. De Moor; J. Deviere; J.-L. Vincent; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Propensity for paternal inheritance of de novo mutations in Alexander disease - Rong Li; Anne B. Johnson; Gajja S. Salomons; Marjo S. van der Knaap; Diana Rodriguez; Odile Boespflug-Tanguy; J. Rafael Gorospe; James E. Goldman; Albee Messing; Michael Brenner (Human Genetics, 2006)

The effect of headspace renewal in a Temporary Immersion Bioreactor on plantain (Musa AAB) shoot proliferation and quality - S. Roels; C. Noceda; M. Escalona; J. Sandoval; M.J. Canal; R. Rodriguez; P. Debergh (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

The impacts of climate change in coastal marine systems - Christopher D. G. Harley; A. Randall Hughes; Kristin M. Hultgren; Benjamin G. Miner; Cascade J. B. Sorte; Carol S. Thornber; Laura F. Rodriguez; Lars Tomanek; Susan L. Williams (Ecology Letters, 2006)
Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate‐related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For example, changes in ocean chemistry may be more important than changes in temperature for the performance and survival of many organisms. Ocean circulation, which drives larval transport, will also change, with important consequences for population dynamics. Furthermore, climatic impacts on one or a few ‘leverage species’ may result in sweeping community‐level changes. Finally, synergistic effects between climate and other anthropogenic variables, particularly fishing pressure, will likely exacerbate climate‐induced changes. Efforts to manage and conserve living marine systems in the face of climate change will require improvements to the existing predictive framework. Key directions for future research include identifying key demographic transitions that influence population dynamics, predicting changes in the community‐level impacts of ecologically dominant species, incorporating populations’ ability to evolve (adapt), and understanding the scales over which climate will change and living systems will respond.

Surfactant-Enhanced Desorption of Atrazine and Linuron Residues as Affected by Aging of Herbicides in Soil - M. S. Rodriguez-Cruz; M. J. Sanchez-Martin; M. Sanchez-Camazano (Archives of Environmental Contamination and Toxicology, 2006)

Behavioral alterations in lewis rats following two-day continuous 3-nitropropionic acid administration - J. D. Newcomb; W. D. Brown; A. I. Rodriguez; S. Garbuzova-Davis; S. Saporta; P. R. Sanberg; A. E. Willing (Neurotoxicity Research, 2005)

Optimization of plantain (Musa AAB) micropropagation by temporary immersion system - S. Roels; M. Escalona; I. Cejas; C. Noceda; R. Rodriguez; M. J. Canal; J. Sandoval; P. Debergh (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Induced plant responses to multiple damagers: differential effects on an herbivore and its parasitoid - Cesar Rodriguez-Saona; Jennifer A. Chalmers; Sherosha Raj; Jennifer S. Thaler (Oecologia, 2005)

Dengue virus type 2 in Cuba, 1997: conservation of E gene sequence in isolates obtained at different times during the epidemic - R. Rodriguez-Roche; M. Alvarez; T. Gritsun; D. Rosario; S. Halstead; G. Kouri; E. A. Gould; M. G. Guzman (Archives of Virology, 2005)

Effects of Tropospheric Ozone on Potato Plants Protected by the Antioxidant Diphenylamine (DPA) - J. L. Carrasco-Rodriguez; A. Asensi-Fabado; S. Del Valle-Tascon (Water, Air, & Soil Pollution, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Environmental Education as a Component of Multidisciplinary Conservation Programs: Lessons from Conservation Initiatives for Critically Endangered Fruit Bats in the Western Indian Ocean - W. J. TREWHELLA; K. M. RODRIGUEZ‐CLARK; N. CORP; A. ENTWISTLE; S. R. T. GARRETT; E. GRANEK; K. L. LENGEL; M. J. RABOUDE; P. F. REASON; B. J. SEWALL (Conservation Biology, 2005)
Pteropus livingstonii , P. voeltzkowi , and P. rodricensis are three critically endangered fruit bats from western Indian Ocean islands for which multidisciplinary conservation programs have been established that include environmental education programs (EEPs). We describe these EEPs in terms of the strategies used to achieve them and evaluate the educational and conservation outcomes and impacts of the programs. Educational outputs (including posters, stickers, videos, lesson plans, and workshops), primarily linking human needs to the ecosystem services provided by bats, were delivered to schools and community groups, and local environmental educators were trained to further develop the EEPs. Outcomes included increased local awareness about the bats and their conservation, training of environmental educators, inclusion of bat conservation and environmental issues in the school curricula, and establishment of community‐based environmental nongovernmental organizations (NGOs). Extensive prior planning, presentations in local languages, distribution of outputs through existing networks of educators, training of local educators, establishment of local environmental NGOs, and local capacity‐building were all associated with these EEPs achieving their goals in the under‐resourced island locations where these bats are found. The EEPs were also important in the development of other components of their respective conservation programs, such as population monitoring programs. Although long‐term conservation impacts, particularly tackling habitat loss, are slow to materialize and social and economic issues need to be addressed, these EEPs have already had important outcomes and have established the foundation for future conservation actions.

The Role of Fungal Symbioses in the Adaptation of Plants to High Stress Environments - Russell J. Rodriguez; Regina S. Redman; Joan M. Henson (Mitigation and Adaptation Strategies for Global Change, 2004)

Transgenic Rice as a Vehicle for the Production of the Industrial Enzyme Transglutaminase - M.I. Claparols; L. Bassie; B. Miro; S. Del Duca; J. Rodriguez-Montesinos; P. Christou; D. Serafini-Fracassini; T. Capell (Transgenic Research, 2004)

Experimental Study of the Formation of Chlorination By-Products in Potable Water of Quebec City, Canada - M. J. Rodriguez; M. Huard; J.-B. Srodes (Bulletin of Environmental Contamination and Toxicology, 2004)

A comparative study of the expression of monoamine oxidase-A and -B mRNA and protein in non-CNS human tissues - S. D. Sivasubramaniam; C. C. Finch; M. J. Rodriguez; N. Mahy; E. E. Billett (Cell and Tissue Research, 2003)

The Effect of perturbations on phytoplankton assemblages in a deep reservoir (Vouglans, France) - M. Leitão; S.M. Morata; S. Rodriguez; J.P. Vergon (Hydrobiologia, 2003)

Comparative analysis of superfamilies of NBS-encoding disease resistance gene analogs in cultivated and wild apple species - S.-Y. Lee; J.-S. Seo; M. Rodriguez-Lanetty; D.-H. Lee (Molecular Genetics and Genomics, 2003)

Calcium, vitamin D, dairy products, and risk of colorectal cancer in the Cancer Prevention Study II Nutrition Cohort (United States) - Marjorie L. McCullough; Andrea S. Robertson; Carmen Rodriguez; Eric J. Jacobs; Ann Chao; Carolyn Jonas; Eugenia E. Calle; Walter C. Willett; Michael J. Thun (Cancer Causes & Control, 2003)

Mineralization of Clapper Rail Eggshell from a Contaminated Salt Marsh System - A. B. Rodriguez-Navarro; K. F. Gaines; C. S. Romanek; G. R. Masson (Archives of Environmental Contamination and Toxicology, 2002)

The reliability of immunohistochemistry as a prescreening method for the diagnosis of hereditary nonpolyposis colorectal cancer (HNPCC) – Results of an international collaborative study - Wolfram Müller; Lawrence J. Burgart; Ruth Krause-Paulus; Stephen N. Thibodeau; M. Almeida; T. Brocker Edmonston; C. R. Boland; C. Sutter; J. R. Jass; A. Lindblom; J. Lubinski; K. MacDermot; et al. (Familial Cancer, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Plant species diversity as a driver of early succession in abandoned fields: a multi-site approach - W. H. Van der Putten; S. R. Mortimer; K. Hedlund; C. Van Dijk; V. K. Brown; J. Lepä; C. Rodriguez-Barrueco; J. Roy; T. A. Diaz Len; D. Gormsen; G. W. Korthals; S. Lavorel; et al. (Oecologia, 2000)

Patterns of inpatient surgeries for the top four cancers in the United States, National Hospital Discharge Survey, 1988–95 - Phyllis A. Wingo; Jodie L. Guest; LaMar McGinnis; Daniel S. Miller; Carmen Rodriguez; Cheryll J. Cardinez; Brian Morrow; Michael J. Thun (Cancer Causes & Control, 2000)

Brown adipose tissue response to cafeteria diet-feeding involves induction of the UCP2 gene and is impaired in female rats as compared to males - P. Roca; A.M. Rodriguez; P. Oliver; M.L. Bonet; S. Quevedo; C. Picó; A. Palou (Pflügers Archiv - European Journal of Physiology, 1999)

The correlation of the gene csoS2 of the carboxysome operon with two polypeptides of the carboxysome in Thiobacillus neapolitanus - S. H. Baker; S. C. Lorbach; M. Rodriguez-Buey; Donna S. Williams; Henry C. Aldrich; J. M. Shively (Archives of Microbiology, 1999)

Brown adipose tissue response to cafeteria diet-feeding involves induction of the UCP2 gene and is impaired in female rats as compared to males - P. Roca; A.M. Rodriguez; P. Oliver; M.L. Bonet; S. Quevedo; C. Picó; A. Palou (Pflügers Archiv - European Journal of Physiology, 1999)

A statistical approach to study the dynamics of micropropagation rates, using banana ( Musa spp.) as an example - B. M. J. Mendes; S. B. Filippi; C. G. B. Demétrio; A. P. M. Rodriguez (Plant Cell Reports, 1999)

Differential expression of rice α-amylase genes during seedling development under anoxia - Y.-S. Hwang; B.R. Thomas; R.L. Rodriguez (Plant Molecular Biology, 1999)

Controlling nitrous oxide emissions from grassland livestock production systems - O. Oenema; G. Gebauer; M. Rodriguez; A. Sapek; S.C. Jarvis; W.J. Corré; S. Yamulki (Nutrient Cycling in Agroecosystems, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Effects of ? 2 -microglobulin mutations on the alpha-1 helical region of H2-L d - Carla S. Schultz; Rafael A. Rodriguez; Eleanor A. Chew; M. C. Nieto; Christian Dimaano; Fung-Mee Li; Marjorie D. Santos (Immunogenetics, 1998)

Neurological and functional effects of short-term exposure to hand-arm vibration - J. Malchaire; L. S. Rodriguez Diaz; A. Piette; F. Gonçalves Amaral; D. de Schaetzen (International Archives of Occupational and Environmental Health, 1998)

Spatial and temporal patterns of annual precipitation variability over the Iberian Peninsula - C. Rodriguez-Puebla; A. H. Encinas; S. Nieto; J. Garmendia (International Journal of Climatology, 1998)

Three cis-elements required for rice α-amylase Amy3D expression during sugar starvation - Y.-S. Hwang; E.E. Karrer; B.R. Thomas; L. Chen; R.L. Rodriguez (Plant Molecular Biology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Natural Co-Occurence of Fusarium Species (Section Liseola) and Apergillus flavus Group Species, Fumonisin and Aflatoxin in Argentinian Corn - A. Torres; M. L. Ramirez; M. M. Reynoso; M. Y. Rodriguez; S. Chulze (Cereal Research Communications, 1997)

Fusarium and Fumonisins in Corn at Harvest Time: Effect of Fertilization and Planting Area - M. L. Ramirez; A. Torres; M. Rodriguez; C. Castillo; S. Chulze (Cereal Research Communications, 1997)

Reproductive Toxicology of 3,3',4,4'-Tetrachlorobiphenyl in Mice - J. Rodriguez; S. D. Kholkute; W. R. Dukelow (Bulletin of Environmental Contamination and Toxicology, 1997)

Genetic analysis of nonhistone chromosomal protein inheritance in recombinant inbred mouse strains using two-dimensional electrophoresis - Louis S. Ramagli; James E. Womack; Lewis V. Rodriguez (Biochemical Genetics, 1990)

Beta interferon production in primed and unprimed cells infected with human cytomegalovirus - J. E. Rodriguez; T. R. Loepfe; N. S. Swack (Archives of Virology, 1987)

Imide derivatives of 3-nitro-1.8-naphthalic acid: Their inhibitory activity against DNA viruses - A. Garca Gancedo; C. Gil-Fernndez; P. Vilas; S. Perez; E. Paez; F. Rodriguez; M. F. Braa; C. M. Roldn (Archives of Virology, 1982)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1981)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1979)

Fetal infection of the baboon(Papio cynocephalus) with lymphocytic choriomeningitis virus - R. Ackermann; S. S. Kalter; R. L. Heberling; B. McCullough; J. Eichberg; A. R. Rodriguez (Archives of Virology, 1979)

Clinical, virological, and pathological features of herpesvirus SA8 infection in conventional and gnotobiotic infant baboons(Papio cynocephalus) - J. W. Eichberg; B. McCullough; S. S. Kalter; D. E. Thor; A. R. Rodriguez (Archives of Virology, 1976)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)